Purification and drying of graphene oxide
Patent Information
- Application Number
- JP2023069820
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-05-23
- Filing Date
- 2023-04-21
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2038-05-04
Smart Images

Figure 0007632904000001 
Figure 0007632904000002 
Figure 0007632904000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Patent Application No. 62 / 501,999, filed May 5, 2017, and U.S. Provisional Patent Application No. 62 / 509,970, filed May 23, 2017, which are incorporated by reference in their entireties. [Background technology]
[0002] Provided herein are graphene materials, fabrication processes, and devices with improved performance and high throughput. In some embodiments, the present disclosure provides graphene oxide (GO) materials and methods for forming GO materials. Such methods for forming GO materials avoid the shortcomings of current methods and facilitate easy, high-throughput production of GO materials. Summary of the Invention
[0003] The present disclosure provides graphene materials, fabrication processes, and devices with improved performance. In some embodiments, the present disclosure provides graphene oxide (GO) materials and methods of forming GO materials. Such methods of forming GO materials avoid the shortcomings of current graphene processing methods. Features of the subject matter described herein provide high throughput of GO materials with high purity for applications including, but not limited to, inkjet printing, screen printing, printed circuit boards, radio frequency identification chips, smart fabrics, conductive coatings, gravure printing, flexographic printing, batteries, supercapacitors, electrodes, electromagnetic interference shielding, printed transistors, memory, sensors, large area heaters, electronics, membranes, antistatic coatings, and energy storage systems.
[0004] A first aspect provided herein is a method of forming a purified GO material, comprising forming a GO suspension, dehydrating the GO suspension with a first filter to form a dehydrated GO suspension, forming a GO solution comprising the dehydrated GO suspension and a solvent solution, and filtering the GO solution through a second filter. In some embodiments, the method comprises forming a GO suspension, depositing the GO suspension and the solvent solution on the first filter, and filtering the GO solution through the first filter. In some embodiments, the GO suspension comprises GO. In some embodiments, forming the GO suspension comprises the Hummers process.
[0005] In some embodiments, the mass of the GO suspension per area of the first filter is about 3 kilograms per square meter (kg / m 2 ) ~ approx. 30kg / m 2 In some embodiments, the mass of the GO suspension per area of the first filter is at least about 3 kg / m 2 In some embodiments, the mass of the GO suspension per area of the first filter is up to about 30 kg / m 2 In some embodiments, the mass of the GO suspension per area of the first filter is about 3 kg / m 2 ~about 5kg / m 2 , about 3kg / m 2 ~about 8kg / m 2 , about 3kg / m 2 ~Approx. 14kg / m 2 , about 3kg / m 2 ~about 18kg / m 2 , about 3kg / m 2 ~Approx. 22kg / m 2 , about 3kg / m 2 ~Approx. 26kg / m 2 , about 3kg / m 2 ~about 30kg / m 2 , about 5kg / m 2 ~about 8kg / m 2 , about 5kg / m 2 ~Approx. 14kg / m 2 , about 5kg / m 2 ~about 18kg / m2 , about 5kg / m 2 ~Approx. 22kg / m 2 , about 5kg / m 2 ~Approx. 26kg / m 2 , about 5kg / m 2 ~about 30kg / m 2 , about 8kg / m 2 ~Approx. 14kg / m 2 , about 8kg / m 2 ~about 18kg / m 2 , about 8kg / m 2 ~Approx. 22kg / m 2 , about 8kg / m 2 ~Approx. 26kg / m 2 , about 8kg / m 2 ~about 30kg / m 2 , about 14kg / m 2 ~about 18kg / m 2 , about 14kg / m 2 ~Approx. 22kg / m 2 , about 14kg / m 2 ~Approx. 26kg / m 2 , about 14kg / m 2 ~about 30kg / m 2 , about 18kg / m 2 ~Approx. 22kg / m 2 , about 18kg / m 2 ~Approx. 26kg / m 2 , about 18kg / m 2 ~about 30kg / m 2 , about 22kg / m 2 ~Approx. 26kg / m 2 , about 22kg / m 2 ~about 30kg / m 2 , or about 26 kg / m 2 ~about 30kg / m 2 In some embodiments, the mass of the GO suspension per area of the first filter is about 3 kg / m 2 , about 5kg / m 2 , about 8kg / m 2 , about 14kg / m 2 , about 18kg / m 2 , about 22kg / m 2 , about 26kg / m 2 , or about 30 kg / m 2In some embodiments, the mass of the GO suspension per area of the first filter is at least about 3 kg / m 2 , at least about 5 kg / m 2 , at least about 8 kg / m 2 , at least about 14 kg / m 2 , at least about 18 kg / m 2 , at least about 22 kg / m 2 , at least about 26 kg / m 2 , or at least about 30 kg / m 2 In some embodiments, the mass of the GO suspension per area of the first filter is at most about 3 kg / m 2 , up to about 5kg / m 2 , up to about 8kg / m 2 , up to about 14 kg / m 2 , up to about 18 kg / m 2 , up to about 22 kg / m 2 , up to about 26 kg / m 2 , or up to about 30 kg / m 2 It is.
[0006] In some embodiments, the weight percent of GO in the GO suspension is about 0.05% to about 2%. In some embodiments, the weight percent of GO in the GO suspension is at least about 0.05%. In some embodiments, the weight percent of GO in the GO suspension is up to about 2%. In some embodiments, the weight percent of GO in the GO suspension is about 0.05% to about 0.1%, about 0.05% to about 0.2%, about 0.05% to about 0.4%, about 0.05% to about 0.6%, about 0.05% to about 0.8%, about 0.05% to about 1%, about 0.05% to about 1.2%, about 0.05% to about 1.4%, about 0.05% to about 1.6%, about 0.05% to about 1.8%, about 0.05% to about 2%, about 0.1% to about 0.2%, about 0.1% to about 0.4%, about 0.1% ~ about 0.6%, about 0.1% to about 0.8%, about 0.1% to about 1%, about 0.1% to about 1.2%, about 0.1% to about 1.4%, about 0.1% to about 1.6%, about 0.1% to about 1.8%, about 0.1% to about 2%, about 0.2% to about 0.4%, about 0.2% to about 0.6%, about 0.2% to about 0.8%, about 0.2% to about 1%, about 0.2% to about 1.2%, about 0.2% to about 1.4%, about 0.2% to about 1.6%, about 0.2% to about 1.8%, about 0.2% to about 2%, about 0.4% to about 0 .6%, about 0.4% to about 0.8%, about 0.4% to about 1%, about 0.4% to about 1.2%, about 0.4% to about 1.4%, about 0.4% to about 1.6%, about 0.4% to about 1.8%, about 0.4% to about 2%, about 0.6% to about 0.8%, about 0.6% to about 1%, about 0.6% to about 1.2%, about 0.6% to about 1.4%, about 0.6% to about 1.6%, about 0.6% to about 1.8%, about 0.6% to about 2%, about 0.8% to about 1%, about 0.8% to about 1.2%, about 0.8% to about 1.4%, about 0.8% to about 1.6%, about 0.8% to about 1.8%, about 0.8% to about 2%, about 1% to about 1.2%, about 1% to about 1.4%, about 1% to about 1.6%, about 1% to about 1.8%, about 1% to about 2%, about 1.2% to about 1.4%, about 1.2% to about 1.6%, about 1.2% to about 1.8%, about 1.2% to about 2%, about 1.4% to about 1.6%, about 1.4% to about 1.8%, about 1.4% to about 2%, about 1.6% to about 1.8%, about 1.6% to about 2%, or about 1.8% to about 2%.In some embodiments, the mass percentage of GO in the GO suspension is about 0.05%, about 0.1%, about 0.2%, about 0.4%, about 0.6%, about 0.8%, about 1%, about 1.2%, about 1.4%, about 1.6%, about 1.8%, or about 2%. In some embodiments, the mass percentage of GO in the GO suspension is at least about 0.05%, at least about 0.1%, at least about 0.2%, at least about 0.4%, at least about 0.6%, at least about 0.8%, at least about 1%, at least about 1.2%, at least about 1.4%, at least about 1.6%, at least about 1.8%, or at least about 2%. In some embodiments, the weight percentage of GO in the GO suspension is at most about 0.05%, at most about 0.1%, at most about 0.2%, at most about 0.4%, at most about 0.6%, at most about 0.8%, at most about 1%, at most about 1.2%, at most about 1.4%, at most about 1.6%, at most about 1.8%, or at most about 2%.
[0007] In some embodiments, depositing the GO suspension and the solvent solution onto the first filter includes depositing the GO suspension onto the first filter and then depositing the solvent solution onto the GO suspension on the first filter.
[0008] In some embodiments, the solvent solution comprises water, a solvent, or any combination thereof. In some embodiments, the solvent comprises an organic solvent. In some embodiments, the solvent comprises acetic acid, acetone, acetonitrile, benzene, 1-butanol, 2-butanol, 2-butanone, t-butyl alcohol, carbon tetrachloride, chlorobenzene, chloroform, cyclohexane, 1,2-dichloroethane, diethylene glycol, diethyl ether, diglyme, diethylene glycol, dimethyl ether, 1,2-dimethoxyethane, dimethylformamide, dimethylsulfoxide, 1,4-dioxane, ethanol, ethyl acetate, ethylene glycol, glycerin, heptane, hexamethylphosphoramide, hexamethylphosphite triamide, hexane, methanol, methyl t-butyl ether, methylene chloride, N-methyl-2-pyrrolidinone, nitromethane, pentane, petroleum ether, 1-propanol, 2-propanol, pyridine, tetrahydrofuran, toluene, triethylamine, o-xylene, m-xylene, p-xylene, or any combination thereof. In some embodiments, the organic solvent comprises a polar organic solvent. In some embodiments, the polar organic solvent comprises ethyl acetate, tetrahydrofuran, dichloromethane, acetone, acetonitrile, dimethylformamide, dimethylsulfoxide, acetic acid, n-butanol, isopropanol, n-propanol, ethanol, methanol, formic acid, or any combination thereof. In some embodiments, the polar organic solvent comprises a protic polar organic solvent. In some embodiments, the protic polar organic solvent comprises acetic acid, n-butanol, isopropanol, n-propanol, ethanol, methanol, formic acid, or any combination thereof. In some embodiments, the polar organic solvent comprises an alcohol.In some embodiments, the alcohol comprises methanol, ethanol, propan-2-ol, butan-1-ol, pentan-1-ol, hexadecan-1-ol, ethane-1,2-diol, propane-1,2-diol, propane-1,2,3-triol, butane-1,2,3,4-tetraol, pentane-1,2,3,4,5-pentol, hexane-1,2,3,4,5,6-hexol, heptane-1,2,3,4,5,6,7-heptol, prop-2-en-1-ol, 3,7-dimethylocta-2,6-dien-1-ol, prop-2-yn-1-ol, cyclohexane-1,2,3,4,5,6-hexol, 2-(2-propyl)-5-methyl-cyclohexan-1-ol, or any combination thereof. In some embodiments, the solvent comprises methanol, ethanol, acetone, dimethylsulfoxide, dimethylformamide, N-methyl-2-pyrrolidone, or any combination thereof.
[0009] In some embodiments, the solvent has a vapor pressure of about 0.05 kilopascals (kPa) to about 30 kPa. In some embodiments, the solvent has a vapor pressure of at least about 0.05 kPa. In some embodiments, the solvent has a vapor pressure of at most about 30 kPa. In some embodiments, the solvent has a vapor pressure of about 0.05 kPa to about 0.1 kPa, about 0.05 kPa to about 1 kPa, about 0.05 kPa to about 3 kPa, about 0.05 kPa to about 6 kPa, about 0.05 kPa to about 9 kPa, about 0.05 kPa to about 15 kPa, about 0.05 kPa to about 20 kPa, about 0.05 kPa to about 25 kPa, about 0.05 kPa to about 30 kPa, ...25 kPa, about 0.05 kPa to about 30 kPa, about 0.1 kPa, about 0.05 kPa to about 1 kPa, about 0.05 kPa to about 1 kPa, about 0.05 kPa to about 1 kPa, about 0.05 kPa to about 25 kPa, about 0.05 kPa to about 30 kPa, about 0.1 kPa, about 0 Pa to about 1 kPa, about 0.1 kPa to about 3 kPa, about 0.1 kPa to about 6 kPa, about 0.1 kPa to about 9 kPa, about 0.1 kPa to about 15 kPa, about 0.1 kPa to about 20 kPa, about 0.1 kPa to about 25 kPa, about 0.1 kPa to about 30 kPa, about 1 kPa to about 3 kPa, about 1 kPa to about 6 kPa, about 1 kPa to about 9 kPa, about 1 kPa to about 15 kPa, about 1 kPa to about 20kPa, about 1kPa to about 25kPa, about 1kPa to about 30kPa, about 3kPa to about 6kPa, about 3kPa to about 9kPa, about 3kPa to about 15kPa, about 3kPa to about 20kPa, about 3kPa to about 25kPa, about 3kPa to about 30kPa, about 6kPa to about 9kPa, about 6kPa to about 15kPa, about 6kPa to about 20kPa, about 6kPa to about 25kPa a, about 6 kPa to about 30 kPa, about 9 kPa to about 15 kPa, about 9 kPa to about 20 kPa, about 9 kPa to about 25 kPa, about 9 kPa to about 30 kPa, about 15 kPa to about 20 kPa, about 15 kPa to about 25 kPa, about 15 kPa to about 30 kPa, about 20 kPa to about 25 kPa, about 20 kPa to about 30 kPa, or about 25 kPa to about 30 kPa. In some embodiments, the solvent has a vapor pressure of about 0.05 kPa, about 0.1 kPa, about 1 kPa, about 3 kPa, about 6 kPa, about 9 kPa, about 15 kPa, about 20 kPa, about 25 kPa, or about 30 kPa.In some embodiments, the solvent has a vapor pressure of at least about 0.05 kPa, at least about 0.1 kPa, at least about 1 kPa, at least about 3 kPa, at least about 6 kPa, at least about 9 kPa, at least about 15 kPa, at least about 20 kPa, at least about 25 kPa, or at least about 30 kPa. In some embodiments, the solvent has a vapor pressure of at most about 0.05 kPa, at most about 0.1 kPa, at most about 1 kPa, at most about 3 kPa, at most about 6 kPa, at most about 9 kPa, at most about 15 kPa, at most about 20 kPa, at most about 25 kPa, or at most about 30 kPa.
[0010] In some embodiments, the weight percent of the solvent in the solvent solution is about 0.1% to about 99%. In some embodiments, the weight percent of the solvent in the solvent solution is at least about 0.1%. In some embodiments, the weight percent of the solvent in the solvent solution is up to about 99%. In some embodiments, the weight percent of the solvent in the solvent solution is about 0.1% to about 1%, about 0.1% to about 5%, about 0.1% to about 10%, about 0.1% to about 15%, about 0.1% to about 20%, about 0.1% to about 30%, about 0.1% to about 40%, about 0.1% to about 50%, about 0.1% to about 60%, about 0.1% to about 80%, about 0.1% to about 99%, about 1% to about 5%, about 1% to about 10%, about 1% to about 15%, about 1% to about 20%, about 1% to about 30%, about 1% to about 40%, about 1% to about 50%, about 1% to about 60%, about 1% to about 80%, about 1% to about 99%, about 5% to about 10%, about 5% to about 15%, about 5% to about 20%, about 5% to about 30%, about 5% to about 40%, about 5% to about 50%, about 5% to about 60%, about 5% to about 80%, about 5% to about 99%, about 10% to about 15%, about 10% to about 20%, about 10 % to about 30%, about 10% to about 40%, about 10% to about 50%, about 10% to about 60%, about 10% to about 80%, about 10% to about 99%, about 15% to about 20%, about 15% to about 30%, about 15% to about 40%, about 15% to about 50%, about 15% to about 60%, about 15% to about 80%, about 15% to about 99%, about 20% to about 30%, about 20% to about 40%, about 20% to about 50%, about 20% to about 60%, about 20% about 80%, about 20% to about 99%, about 30% to about 40%, about 30% to about 50%, about 30% to about 60%, about 30% to about 80%, about 30% to about 99%, about 40% to about 50%, about 40% to about 60%, about 40% to about 80%, about 40% to about 99%, about 50% to about 60%, about 50% to about 80%, about 50% to about 99%, about 60% to about 80%, about 60% to about 99%, or about 80% to about 99%. In some embodiments, the mass percentage of the solvent in the solvent solution is about 0.1%, about 1%, about 5%, about 10%, about 15%, about 20%, about 30%, about 40%, about 50%, about 60%, about 80%, or about 99%.In some embodiments, the weight percent of the solvent in the solvent solution is at least about 0.1%, at least about 1%, at least about 5%, at least about 10%, at least about 15%, at least about 20%, at least about 30%, at least about 40%, at least about 50%, at least about 60%, at least about 80%, or at least about 99%. In some embodiments, the weight percent of the solvent in the solvent solution is up to about 0.1%, up to about 1%, up to about 5%, up to about 10%, up to about 15%, up to about 20%, up to about 30%, up to about 40%, up to about 50%, up to about 60%, up to about 80%, or up to about 99%.
[0011] In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is between about 10% and about 60%. In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is at least about 10%. In some embodiments, In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is up to about 60%. In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is up to about 10% to about 15%, about 10% to about 20%, about 10% to about 25%, about 10% to about 30%, about 10% to about 35%, about 10% to about 40%, about 10% to about 45%, about 10% to about 50%, about 10% to about 55%, about 10% to about 60%, about 15% to about 20%, about 15% to about 30%, about 15% to about 40%, about 15% to about 55%, about 15% to about 60%, about 15% to about 70%, about 15% to about 80%, about 15% to about 90%, about 15% to about 100%, about 15% to about 200%, about 15% to about 300%, about 15% to about 400%, about 15% to about 5 ...500%, about 15% to about 5 %, about 15% to about 25%, about 15% to about 30%, about 15% to about 35%, about 15% to about 40%, about 15% to about 45%, about 15% to about 50%, about 15% to about 55%, about 15% to about 60%, about 20% to about 25%, about 20% to about 30%, about 20% to about 35%, about 20% to about 40%, about 20% to about 45%, about 20% to about 50%, about 20% to about 5 5%, about 20% to about 60%, about 25% to about 30%, about 25% to about 35%, about 25% to about 40%, about 25% to about 45%, about 25% to about 50%, about 25% to about 55%, about 25% to about 60%, about 30% to about 35%, about 30% to about 40%, about 30% to about 45%, about 30% to about 50%, about 30% to about 55%, about 30% to about 60%, about 35% to about 40%, about 35% to about 45%, about 35% to about 50%, about 35% to about 55%, about 35% to about 60%, about 40% to about 45%, about 40% to about 50%, about 40% to about 55%, about 40% to about 60%, about 45% to about 50%, about 45% to about 55%, about 45% to about 60%, about 50% to about 55%, about 50% to about 60%, or about 55% to about 60%. In some embodiments, the mass percentage of the GO suspension and GO suspension in the solvent solution is about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, or about 60%. In some embodiments, the mass percentage of the GO suspension in the GO suspension and solvent solution is at least about 10%, at least about 15%, at least about 20%, at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, at least about 55%, or at least about 60%.In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is at most about 10%, at most about 15%, at most about 20%, at most about 25%, at most about 30%, at most about 35%, at most about 40%, at most about 45%, at most about 50%, at most about 55%, or at most about 60%.
[0012] In some embodiments, filtering the GO solution comprises centrifugal filtration, dead-end filtration, cross-flow filtration, stationary phase filtration, dynamic phase filtration, surface filtration, depth filtration, vacuum filtration, recirculation filtration, or any combination thereof.
[0013] In some embodiments, filtering the GO solution includes dead-end filtration and vacuum filtration, and the water pressure on the GO suspension is about 1 pound per square inch (psi) to about 5 psi. In some embodiments, filtering the GO solution includes dead-end, vacuum filtration, and the water pressure on the GO suspension is at least about 1 psi. In some embodiments, filtering the GO solution includes dead-end, vacuum filtration, and the water pressure on the GO suspension is at most about 5 ... least about 1 psi to about 1.5 psi, at about 1 psi to about 2 psi, at about 1 psi to about 2.5 psi, at about 1 psi to about 3 psi, at about 1 psi to about 3.5 psi, at about 1 psi to about 4 psi, at about 1 psi to about 5 psi, at about 1.5 psi to about 2 psi, at about 1.5 psi to about 2.5 psi, at about 1.5 psi to about 3 psi, at about 1.5 psi to about 3.5 psi, at about 1.5 psi to about 4 psi, at about 1.5 psi to about 5 psi, about 2 psi to about 2.5 psi, about 2 psi to about 3 psi, about 2 psi to about 3.5 psi, about 2 psi to about 4 psi, about 2 psi to about 5 psi, about 2.5 psi to about 3 psi, about 2.5 psi to about 3.5 psi, about 2.5 psi to about 4 psi, about 2.5 psi to about 5 psi, about 3 psi to about 3.5 psi, about 3 psi to about 4 psi, about 3 psi to about 5 psi, about 3.5 psi to about 4 psi, about 3.5 psi to about 5 psi, or about 4 psi to about 5 psi. In some embodiments, filtering the GO solution includes dead-end, vacuum filtration, and the water pressure on the GO suspension is about 1 psi, about 1.5 psi, about 2 psi, about 2.5 psi, about 3 psi, about 3.5 psi, about 4 psi, or about 5 psi. In some embodiments, filtering the GO solution includes dead-end, vacuum filtration, where the water pressure on the GO suspension is at least about 1 psi, at least about 1.5 psi, at least about 2 psi, at least about 2.5 psi, at least about 3 psi, at least about 3.5 psi, at least about 4 psi, or at least about 5 psi.In some embodiments, filtering the GO solution comprises dead-end, vacuum filtration, wherein the water pressure on the GO suspension is at most about 1 psi, at most about 1.5 psi, at most about 2 psi, at most about 2.5 psi, at most about 3 psi, at most about 3.5 psi, at most about 4 psi, or at most about 5 psi.
[0014] In some embodiments, the first filter comprises a Buchner funnel, a surface filter, a sieve, a filter paper, a belt filter, a drum filter, a crossflow filter, a screen filter, a depth filter, a polymeric membrane, a ceramic membrane, a stainless steel filter, a stainless steel mesh, a carbon fiber mesh, a microfilter, an ultrafiltration filter, a membrane, or any combination thereof. In some embodiments, the first filter comprises a stainless steel, dead-end Buchner funnel.
[0015] In some embodiments, the first filter has a pore size of about 0.5 micrometers (μm) to about 100 μm. In some embodiments, the first filter has a pore size of at least about 0.5 μm. In some embodiments, the first filter has a pore size of at most about 100 μm. In some embodiments, the first filter has a thickness of about 0.5 μm to about 1 μm, about 0.5 μm to about 2 μm, about 0.5 μm to about 5 μm, about 0.5 μm to about 10 μm, about 0.5 μm to about 20 μm, about 0.5 μm to about 30 μm, about 0.5 μm to about 40 μm, about 0.5 μm to about 50 μm, about 0.5 μm to about 60 μm, about 0.5 μm to about 80 μm, about 0.5 μm to about 100 μm, about 1 μm to about 2 μm, about 1 μm to about 5 μm, about 1 μm to about 10 μm, or about 1 μm to about 20 μm. m, about 1 μm to about 30 μm, about 1 μm to about 40 μm, about 1 μm to about 50 μm, about 1 μm to about 60 μm, about 1 μm to about 80 μm, about 1 μm to about 100 μm, about 2 μm to about 5 μm, about 2 μm to about 10 μm, about 2 μm to about 20 μm, Approximately 2 μm to approximately 30 μm, approximately 2 μm to approximately 40 μm, approximately 2 μm to approximately 50 μm, approximately 2 μm to approximately 60 μm, approximately 2 μm to approximately 80 μm, approximately 2 μm to approximately 100 μm, approximately 5 μm to approximately 10 μm, approximately 5 μm to approximately 20 μm, approximately 5 μm to approximately 30 μm, approximately 5 5μm to 50μm, 5μm to 60μm, 5μm to 80μm, 5μm to 100μm, 10μm to 20μm, 10μm to 30μm, 10μm to 40μm, 10μm to 50μm , about 10 μm to about 60 μm, about 10 μm to about 80 μm, about 10 μm to about 100 μm, about 20 μm to about 30 μm, about 20 μm to about 40 μm, about 20 μm to about 50 μm, about 20 μm to about 60 μm, about 20 μm to about 80 μm, about 20 μm The pore size is from about 30 μm to about 100 μm, from about 30 μm to about 40 μm, from about 30 μm to about 50 μm, from about 30 μm to about 60 μm, from about 30 μm to about 80 μm, from about 30 μm to about 100 μm, from about 40 μm to about 50 μm, from about 40 μm to about 60 μm, from about 40 μm to about 80 μm, from about 40 μm to about 100 μm, from about 50 μm to about 60 μm, from about 50 μm to about 80 μm, from about 50 μm to about 100 μm, from about 60 μm to about 80 μm, from about 60 μm to about 100 μm, or from about 80 μm to about 100 μm.In some embodiments, the first filter has a pore size of about 0.5 μm, about 1 μm, about 2 μm, about 5 μm, about 10 μm, about 20 μm, about 30 μm, about 40 μm, about 50 μm, about 60 μm, about 80 μm, or about 100 μm. In some embodiments, the first filter has a pore size of at least about 0.5 μm, at least about 1 μm, at least about 2 μm, at least about 5 μm, at least about 10 μm, at least about 20 μm, at least about 30 μm, at least about 40 μm, at least about 50 μm, at least about 60 μm, at least about 80 μm, or at least about 100 μm. In some embodiments, the first filter has a pore size of at most about 0.5 μm, at most about 1 μm, at most about 2 μm, at most about 5 μm, at most about 10 μm, at most about 20 μm, at most about 30 μm, at most about 40 μm, at most about 50 μm, at most about 60 μm, at most about 80 μm, or at most about 100 μm.
[0016] Some embodiments further include dehydrating the GO suspension, hi some embodiments, the GO suspension is dehydrated using a second filter prior to depositing the GO suspension and solvent solution onto the first filter.
[0017] In some embodiments, dewatering the GO suspension comprises centrifugal filtration, dead-end filtration, cross-flow filtration, stationary phase filtration, dynamic phase filtration, surface filtration, depth filtration, vacuum filtration, recirculation filtration, or any combination thereof. In some embodiments, the second filter comprises a Büchner funnel, surface filter, sieve, filter paper, belt filter, drum filter, cross-flow filter, screen filter, depth filter, polymeric membrane, ceramic membrane, stainless steel filter, stainless steel mesh, carbon fiber mesh, microfilter, ultrafiltration filter, membrane, or any combination thereof. In some embodiments, the second filter comprises a stainless steel, dead-end Büchner funnel.
[0018] In some embodiments, the second filter has a pore size of about 0.5 μm to about 100 μm. In some embodiments, the second filter has a pore size of at least about 0.5 μm. In some embodiments, the second filter has a pore size of at most about 100 μm. In some embodiments, the second filter has a thickness of about 0.5 μm to about 1 μm, about 0.5 μm to about 2 μm, about 0.5 μm to about 5 μm, about 0.5 μm to about 10 μm, about 0.5 μm to about 20 μm, about 0.5 μm to about 30 μm, about 0.5 μm to about 40 μm, about 0.5 μm to about 50 μm, about 0.5 μm to about 60 μm, about 0.5 μm to about 80 μm, about 0.5 μm to about 100 μm, about 1 μm to about 2 μm, about 1 μm to about 5 μm, about 1 μm to about 10 μm, or about 1 μm to about 20 μm. m, about 1 μm to about 30 μm, about 1 μm to about 40 μm, about 1 μm to about 50 μm, about 1 μm to about 60 μm, about 1 μm to about 80 μm, about 1 μm to about 100 μm, about 2 μm to about 5 μm, about 2 μm to about 10 μm, about 2 μm to about 20 μm, Approximately 2 μm to approximately 30 μm, approximately 2 μm to approximately 40 μm, approximately 2 μm to approximately 50 μm, approximately 2 μm to approximately 60 μm, approximately 2 μm to approximately 80 μm, approximately 2 μm to approximately 100 μm, approximately 5 μm to approximately 10 μm, approximately 5 μm to approximately 20 μm, approximately 5 μm to approximately 30 μm, approximately 5 5μm to 50μm, 5μm to 60μm, 5μm to 80μm, 5μm to 100μm, 10μm to 20μm, 10μm to 30μm, 10μm to 40μm, 10μm to 50μm , about 10 μm to about 60 μm, about 10 μm to about 80 μm, about 10 μm to about 100 μm, about 20 μm to about 30 μm, about 20 μm to about 40 μm, about 20 μm to about 50 μm, about 20 μm to about 60 μm, about 20 μm to about 80 μm, about 20 μm The pore size is from about 30 μm to about 100 μm, from about 30 μm to about 40 μm, from about 30 μm to about 50 μm, from about 30 μm to about 60 μm, from about 30 μm to about 80 μm, from about 30 μm to about 100 μm, from about 40 μm to about 50 μm, from about 40 μm to about 60 μm, from about 40 μm to about 80 μm, from about 40 μm to about 100 μm, from about 50 μm to about 60 μm, from about 50 μm to about 80 μm, from about 50 μm to about 100 μm, from about 60 μm to about 80 μm, from about 60 μm to about 100 μm, or from about 80 μm to about 100 μm.In some embodiments, the second filter has a pore size of about 0.5 μm, about 1 μm, about 2 μm, about 5 μm, about 10 μm, about 20 μm, about 30 μm, about 40 μm, about 50 μm, about 60 μm, about 80 μm, or about 100 μm. In some embodiments, the second filter has a pore size of at least about 0.5 μm, at least about 1 μm, at least about 2 μm, at least about 5 μm, at least about 10 μm, at least about 20 μm, at least about 30 μm, at least about 40 μm, at least about 50 μm, at least about 60 μm, at least about 80 μm, or at least about 100 μm. In some embodiments, the second filter has a pore size of at most about 0.5 μm, at most about 1 μm, at most about 2 μm, at most about 5 μm, at most about 10 μm, at most about 20 μm, at most about 30 μm, at most about 40 μm, at most about 50 μm, at most about 60 μm, at most about 80 μm, or at most about 100 μm.
[0019] In some embodiments, the second filter is the first filter. In some embodiments, the second filter and the first filter are separate filters.
[0020] In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by about 45% to about 99%. In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by at least about 45%. In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by up to about 99%. In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by about 45% to about 50%, about 45% to about 55%, about 45% to about 60%, about 45% to about 65%, about 45% to about 70%, about 45% to about 75%, about 45% to about 80%, about 45% to about 85%, about 45% to about 90%, about 45% to about 99%, about 50% to about 55%. , about 50% to about 60%, about 50% to about 65%, about 50% to about 70%, about 50% to about 75%, about 50% to about 80%, about 50% to about 85%, about 50% to about 90%, about 50% to about 99%, about 55% to about 60%, about 55% to about 65%, about 55% to about 70%, about 55% to about 75%, about 55% to about 80%, about 55% to about 85%, about 55% to about 90% , about 55% to about 99%, about 60% to about 65%, about 60% to about 70%, about 60% to about 75%, about 60% to about 80%, about 60% to about 85%, about 60% to about 90%, about 60% to about 99%, about 65% to about 70%, about 65% to about 75%, about 65% to about 80%, about 65% to about 85%, about 65% to about 90%, about 65% to about 99%, about 70% to about 75% , about 70% to about 80%, about 70% to about 85%, about 70% to about 90%, about 70% to about 99%, about 75% to about 80%, about 75% to about 85%, about 75% to about 90%, about 75% to about 99%, about 80% to about 85%, about 80% to about 90%, about 80% to about 99%, about 85% to about 90%, about 85% to about 99%, or about 90% to about 99%. In some embodiments, by dehydrating the GO suspension, the water content of the GO suspension is reduced by about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, about 90%, or about 99%.In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by at least about 45%, at least about 50%, at least about 55%, at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, at least about 85%, at least about 90%, or at least about 99%. In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by up to about 45%, up to about 50%, up to about 55%, up to about 60%, up to about 65%, up to about 70%, up to about 75%, up to about 80%, up to about 85%, up to about 90%, or up to about 99%.
[0021] In some embodiments, the weight percent of GO in the GO suspension after dehydrating the GO suspension is about 40% to about 90%. In some embodiments, the weight percent of GO in the GO suspension after dehydrating the GO suspension is at least about 40%. In some embodiments, the weight percent of GO in the GO suspension after dehydrating the GO suspension is up to about 90. In some embodiments, the weight percent of GO in the GO suspension after dehydrating the GO suspension is about 40% to about 45%, about 40% to about 50%, about 40% to about 55%, about 40% to about 60%, about 40% to about 65%, about 40% to about 70%, about 40% to about 75%, about 40% to about 80%, about 40% to about 85%, about 40% to about 90%, about 45% to about 50%, about 45% to about 55%, about 45% to about 60%, about 45% to about 65%, about 45% to about 70%, about 45% to about 75%, about 45% to about 80%, about 45% to about 85%, about 45% to about 90%, about 50% to about 55%, about 50% to about 60%, about 50% to about 65%, about 50% to about 70%, about 50% to about 75%, about 50% to about 80%, about 50% to about 85%, about 50% to about 90%, about 55% to about 60%, about 55% to about 65%, about 55% to about 70%, about 55% to about 75%, about 55% to about 80%, about 55% to about 85%, about 55% to about 90%, about 60% to about 65%, about 60% to about 70%, about 60% to about 75%, about 60% to about 80%, about 60% to about 85%, about 60% to about 90%, about 65% to about 70%, about 65% to about 75%, about 65% to about 80%, about 65% to about 85%, about 65% to about 90%, about 70% to about 75%, about 70% to about 80%, about 70% to about 85%, about 70% to about 90%, about 75% to about 80%, about 75% to about 85%, about 75% to about 90%, about 80% to about 85%, about 80% to about 90%, or about 85% to about 90%. In some embodiments, the mass percentage of GO in the GO suspension after dehydrating the GO suspension is about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, or about 90%.In some embodiments, after the GO suspension is dehydrated, the mass percentage of GO in the GO suspension is at least about 40%, at least about 45%, at least about 50%, at least about 55%, at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, at least about 85%, or at least about 90%. In some embodiments, after the GO suspension is dehydrated, the mass percentage of GO in the GO suspension is at most about 40%, at most about 45%, at most about 50%, at most about 55%, at most about 60%, at most about 65%, at most about 70%, at most about 75%, at most about 80%, at most about 85%, or at most about 90%.
[0022] Some embodiments further include drying the GO suspension and the solvent solution. In some embodiments, drying the GO suspension is performed by air blowing, dry evaporation, heating (e.g., oven heating), freeze drying, or any combination thereof. In some embodiments, the dry evaporation is performed at ambient temperature. In some embodiments, the air blowing is performed with a dry gas stream. In some embodiments, the air blowing is performed with a dry gas stream at a pressure of about 10 psi to about 30 psi.
[0023] In some embodiments, heating (e.g., oven heating) is carried out at a temperature of about 10° C. to about 50° C. In some embodiments, heating is carried out at a temperature of at least about 10° C. In some embodiments, heating is carried out at a temperature of up to about 50° C. In some embodiments, heating is carried out at a temperature of about 10° C. to about 15° C., about 10° C. to about 20° C., about 10° C. to about 25° C., about 10° C. to about 30° C., about 10° C. to about 35° C., about 10° C. to about 40° C., about 10° C. to about 45° C., about 10° C. to about 50° C., about 15° C. to about 20° C., about 15° C. to about 25° C., about 15° C. to about 30° C., about 15° C. to about 35° C., about 15° C. to about 40° C., about 15° C. to about 45° C., about 15° C. to about 50° C., about 20° C. to about 25° C., about 20° C. to about 30° C., about 20° C. to about 35° C. ℃, about 20 ° C to about 40 ° C, about 20 ° C to about 45 ° C, about 20 ° C to about 50 ° C, about 25 ° C to about 30 ° C, about 25 ° C to about 35 ° C, about 25 ° C to about 40 ° C, about 25 ° C to about 45 ° C, about 25 ° C to about 50 ° C, about 30 ° C to about 35 ° C, about 30 ° C to about 40 ° C, about 30 ° C to about 45 ° C, about 30 ° C to about 50 ° C, about 35 ° C to about 40 ° C, about 35 ° C to about 45 ° C, about 35 ° C to about 50 ° C, about 40 ° C to about 45 ° C, about 40 ° C to about 50 ° C, or about 45 ° C to about 50 ° C. In some embodiments, heating is performed at a temperature of about 10 ° C, about 15 ° C, about 20 ° C, about 25 ° C, about 30 ° C, about 35 ° C, about 40 ° C, about 45 ° C, or about 50 ° C. In some embodiments, heating is carried out at a temperature of at least about 10° C., at least about 15° C., at least about 20° C., at least about 25° C., at least about 30° C., at least about 35° C., at least about 40° C., at least about 45° C., or at least about 50° C. In some embodiments, heating is carried out at a temperature of up to about 10° C., up to about 15° C., up to about 20° C., up to about 25° C., up to about 30° C., up to about 35° C., up to about 40° C., up to about 45° C., or up to about 50° C.
[0024] In some embodiments, the weight percent of GO in the GO suspension after drying the GO suspension is about 30% to about 90%. In some embodiments, the weight percent of GO in the GO suspension after drying the GO suspension is at least about 30%. In some embodiments, the weight percent of GO in the GO suspension after drying the GO suspension is up to about 90%. In some embodiments, the weight percent of GO in the GO suspension after drying the GO suspension is about 30% to about 35%, about 30% to about 40%, about 30% to about 45%, about 30% to about 50%, about 30% to about 55%, about 30% to about 60%, about 30% to about 65%, about 30% to about 70%, about 30% to about 75%, about 30% to about 80%, about 30% to about 90%, about 35% to about 40%, about 35% to about 45%, about 35% to about 5 ... 5% to about 50%, about 35% to about 55%, about 35% to about 60%, about 35% to about 65%, about 35% to about 70%, about 35% to about 75%, about 35% to about 80%, about 35% to about 90%, about 40% to about 45%, about 40% to about 50%, about 40% to about 55%, about 40% to about 60%, about 40% to about 65%, about 40% to about 70%, about 40% to about 75%, about 40% to about 80%, about 40% to about 90%, about 45% to about 50%, About 45% to about 55%, about 45% to about 60%, about 45% to about 65%, about 45% to about 70%, about 45% to about 75%, about 45% to about 80%, about 45% to about 90%, about 50% to about 55%, about 50% to about 60%, about 50% to about 65%, about 50% to about 70%, about 50% to about 75%, about 50% to about 80%, about 50% to about 90%, about 55% to about 60%, about 55% to about 65%, about 55% to about 70%, about 55% to about 75 %, about 55% to about 80%, about 55% to about 90%, about 60% to about 65%, about 60% to about 70%, about 60% to about 75%, about 60% to about 80%, about 60% to about 90%, about 65% to about 70%, about 65% to about 75%, about 65% to about 80%, about 65% to about 90%, about 70% to about 75%, about 70% to about 80%, about 70% to about 90%, about 75% to about 80%, about 75% to about 90%, or about 80% to about 90%. In some embodiments, after the GO suspension is dried, the mass percentage of GO in the GO suspension is about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, or about 90%.In some embodiments, the weight percent of GO in the GO suspension after drying is at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, at least about 55%, at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, or at least about 90%. In some embodiments, the weight percent of GO in the GO suspension after drying is at most about 30%, at most about 35%, at most about 40%, at most about 45%, at most about 50%, at most about 55%, at most about 60%, at most about 65%, at most about 70%, at most about 75%, at most about 80%, or at most about 90%.
[0025] In some embodiments, the GO powder is formed by drying the GO suspension. In some embodiments, the GO powder is anhydrous, intercalated, exfoliated, or any combination thereof. In some embodiments, the GO powder comprises single-layer GO. In some embodiments, the GO powder is dispersible in water, polar solvents, or any combination thereof.
[0026] In some embodiments, the GO material is water-based, hi some embodiments, the water-based material comprises an ink, a paste, a solution, a fluid, a liquid, a paint, a dye, a coating, or a compound.
[0027] In some embodiments, the GO material has a viscosity of about 800 m 2 / g ~ approx. 2,400m 2 In some embodiments, the GO material has a surface area of at least about 800 m / g. 2 / g. In some embodiments, the GO material has a surface area of up to about 2,400 m 2 / g. In some embodiments, the GO material has a surface area of about 800 m 2 / g ~ approx. 1,000m 2 / g, approx. 800m 2 / g ~ approx. 1,200m 2 / g, approx. 800m 2 / g~about 1,400m 2 / g, about 800m 2 / g~about 1,600m 2 / g, about 800m 2 / g~about 1,800m 2 / g, about 800m 2 / g~about 2,000m 2 / g, about 800m 2 / g~about 2,200m 2 / g, about 800m 2 / g~about 2,400m 2 / g, about 1,000m 2 / g~about 1,200m 2 / g, about 1,000m 2 / g~about 1,400m 2 / g, about 1,000m 2 / g~about 1,600m 2 / g, about 1,000m 2 / g~about 1,800m 2 / g, about 1,000m 2 / g~about 2,000m 2 / g, about 1,000m 2 / g~about 2,200m 2 / g, about 1,000m 2 / g~about 2,400m 2 / g, about 1,200m 2 / g~about 1,400m 2 / g, about 1,200m 2 / g~about 1,600m 2 / g, about 1,200m 2 / g~about 1,800 m 2 / g, about 1,200m 2 / g~about 2,000m 2 / g, about 1,200m 2 / g~about 2,200m 2 / g, about 1,200m 2 / g~about 2,400m 2 / g, about 1,400m 2 / g~about 1,600m 2 / g, about 1,400m 2 / g~about 1,800m 2 / g, about 1,400m 2 / g~about 2,000m 2 / g, approx. 1,400m 2 / g ~ approx. 2,200m 2 / g, approx. 1,400m 2 / g ~ approx. 2,400m 2 / g, approx. 1,600m 2 / g ~ approx. 1,800m 2 / g, approx. 1,600m 2 / g ~ approx. 2,000m 2 / g, approx. 1,600m 2 / g ~ approx. 2,200m 2 / g, approx. 1,600m 2 / g ~ approx. 2,400m 2 / g, approx. 1,800m 2 / g ~ approx. 2,000m 2 / g, approx. 1,800m 2 / g ~ approx. 2,200m 2 / g, approx. 1,800m 2 / g ~ approx. 2,400m 2 / g, approx. 2,000m 2 / g ~ approx. 2,200m 2 / g, approx. 2,000m 2 / g ~ approx. 2,400m 2 / g, or approximately 2,200 m 2 / g ~ approx. 2,400m 2 / g. In some embodiments, the GO material has a surface area of about 800 m 2 / g, approx. 1,000m 2 / g, approx. 1,200m 2 / g, approx. 1,400m 2 / g, approx. 1,600m 2 / g, approx. 1,800m 2 / g, approx. 2,000m 2 / g, approx. 2,200m 2 / g, or approximately 2,400 m 2 / g surface area.
[0028] In some embodiments, the GO material has a conductivity of about 0.1 Siemens per meter (S / m) to about 5 S / m. In some embodiments, the GO material has a conductivity of at least about 0.1 S / m. In some embodiments, the GO material has a conductivity of up to about 5 S / m. In some embodiments, the GO material has a conductivity of about 0.1 S / m to about 0.2 S / m, about 0.1 S / m to about 0.5 S / m, about 0.1 S / m to about 0.75 S / m, about 0.1 S / m to about 1 S / m, about 0.1 S / m to about 2 S / m, about 0.1 S / m to about 3 S / m, about 0.1 S / m to about 4 S / m, about 0.1 S / m to about 5 S / m, about 0.2S / m to about 0.5S / m, about 0.2S / m to about 0.75S / m, about 0.2S / m to about 1S / m, about 0.2S / m to about 2S / m, about 0.2S / m~Approx. 3S / m, Approx. 0.2S / m~Approx. 4S / m, Approx. 0.2S / m~Approx. 5S / m, Approx. 0.5S / m~Approx. 0.75S / m, Approx. 0.5S / m~Approx. 1S / m, about 0.5S / m to about 2S / m, about 0.5S / m to about 3S / m, about 0.5S / m to about 4S / m, about 0.5S / m to about 5S / m, about 0.75 S / m ~ approx. 1S / m, approx. 0.75S / m ~ approx. 2S / m, approx. 0.75S / m ~ approx. 3S / m, approx. 0.75S / m ~ approx. 4S / m, approx. 0.75S / m ~ approx. 5S In some embodiments, the GO material has a conductivity of about 0.1 S / m, about 0.2 S / m, about 0.5 S / m, about 0.75 S / m, about 1 S / m, about 2 S / m, about 3 S / m, about 4 S / m, or about 5 S / m. In some embodiments, the GO material has a conductivity of at least about 0.1 S / m, at least about 0.2 S / m, at least about 0.5 S / m, at least about 0.75 S / m, at least about 1 S / m, at least about 2 S / m, at least about 3 S / m, at least about 4 S / m, or at least about 5 S / m.In some embodiments, the GO material has a conductivity of at most about 0.1 S / m, at most about 0.2 S / m, at most about 0.5 S / m, at most about 0.75 S / m, at most about 1 S / m, at most about 2 S / m, at most about 3 S / m, at most about 4 S / m, or at most about 5 S / m.
[0029] In some embodiments, the GO material has a C:O mass ratio of about 1:3 to about 5:1. In some embodiments, the GO material has a C:O mass ratio of at least about 1:3. In some embodiments, the GO material has a C:O mass ratio of up to about 5:1. In some embodiments, the GO material is from about 1:3 to about 1:2, from about 1:3 to about 1:1, from about 1:3 to about 2:1, from about 1:3 to about 3:1, from about 1:3 to about 4:1, from about 1:3 to about 5:1, from about 1:2 to about 1:1, from about 1:2 to about 2:1, from about 1:2 to about 3:1, from about 1:2 to about 4:1, from about 1:2 to about 5:1, from about 1:1 to about 2:1, from about 1:1 to about 3:1, from about 1:1 to about 4:1, from about 1:1 to about 5:1, from about 2:1 to about 3:1, from about 2:1 to about 4:1, from about 2:1 to about 5:1, from about 3:1 to about In some embodiments, the GO material has a C:O mass ratio of about 1:3, about 1:2, about 1:1, about 2:1, about 3:1, about 4:1, or about 5:1. In some embodiments, the GO material has a C:O mass ratio of at least about 1:3, at least about 1:2, at least about 1:1, at least about 2:1, at least about 3:1, at least about 4:1, or at least about 5:1. In some embodiments, the GO material has a C:O mass ratio of at most about 1:3, at most about 1:2, at most about 1:1, at most about 2:1, at most about 3:1, at most about 4:1, or at most about 5:1. In some embodiments, the GO material has a C:O mass ratio of at most about 1:3, at most about 1:2, at most about 1:1, at most about 2:1, at most about 3:1, at most about 4:1, or at most about 5:1.
[0030] In some embodiments, the GO material has an oxidation rate of about 15% to about 60%. In some embodiments, the GO material has an oxidation rate of at least about 15%. In some embodiments, the GO material has an oxidation rate of up to about 60%. In some embodiments, the GO material is about 15% to about 20%, about 15% to about 25%, about 15% to about 30%, about 15% to about 35%, about 15% to about 40%, about 15% to about 45%, about 15% to about 50%, about 15% to about 55%, about 15% to about 60%, about 20% to about 25%, about 20% to about 30%, about 20% to about 35%, about 20% to about 40%, about 20% to about 45%, about 20% to about 50%, about 20% to about 55%, about 20% to about 60%, about 25% to about 30%, about 25% to about 35%, about 25% to about 40%, about 25% to about 45%, about 25% to about 50%, about The oxidation rate is from about 25% to about 55%, from about 25% to about 60%, from about 30% to about 35%, from about 30% to about 40%, from about 30% to about 45%, from about 30% to about 50%, from about 30% to about 55%, from about 30% to about 60%, from about 35% to about 40%, from about 35% to about 45%, from about 35% to about 50%, from about 35% to about 55%, from about 35% to about 60%, from about 40% to about 45%, from about 40% to about 50%, from about 40% to about 55%, from about 40% to about 60%, from about 45% to about 50%, from about 45% to about 55%, from about 45% to about 60%, from about 50% to about 55%, from about 50% to about 60%, or from about 55% to about 60%. In some embodiments, the GO material has an oxidation rate of about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, or about 60%. In some embodiments, the GO material has an oxidation rate of at least about 15%, at least about 20%, at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, at least about 55%, or at least about 60%. In some embodiments, the GO material has an oxidation rate of up to about 15%, up to about 20%, up to about 25%, up to about 30%, up to about 35%, up to about 40%, up to about 45%, up to about 50%, up to about 55%, or up to about 60%.
[0031] In some embodiments, at least one of the electrical conductivity, surface area, C:O ratio, and oxidation rate of the GO material is measured by methylene blue absorption.
[0032] In some embodiments, the method of the first aspect comprises a process for producing a pulverized product at a rate of about 100 grams per hour squared (g / (h m 2 ))~Approx. 300g / (h m 2 ) of GO material per area of the first filter. In some embodiments, the method of the first aspect can produce a throughput of at least about 100 g / (h m 2 ) of GO material per area of the first filter. In some embodiments, the method of the first aspect can produce a throughput of GO material per area of the first filter of up to about 300 g / (h m 2 ) of GO material per area of the first filter. In some embodiments, the method of the first aspect can produce a throughput of about 100 g / (h m 2 ) ~ approx. 125g / (h m 2 ), approx. 100g / (h m 2 ) ~ approx. 150g / (h m 2 ), approx. 100g / (h m 2 ) ~ approx. 175g / (h m 2 ), approx. 100g / (h m 2 ) ~ approx. 200g / (h m 2 ), approx. 100g / (h m 2 ) ~ approx. 225g / (h m 2 ), approx. 100g / (h m 2 ) ~ approx. 250g / (h m 2 ), approx. 100g / (h m 2 ) ~ approx. 275g / (h m 2 ), approx. 100g / (h m 2 ) ~ approx. 300g / (h m 2 ), approx. 125g / (h m 2 ) ~ approx. 150g / (h m 2 ), approx. 125g / (h m 2 ) ~ approx. 175g / (h m 2 ), approx. 125g / (h m 2 ) ~ approx. 200g / (h m 2 ), approx. 125g / (h m2 )~about 225g / (h·m 2 ), about 125g / (h·m 2 )~about 250g / (h·m 2 ), about 125g / (h·m 2 )~about 275g / (h·m 2 ), about 125g / (h·m 2 )~about 300g / (h·m 2 ), about 150g / (h·m 2 )~about 175g / (h·m 2 ), about 150g / (h·m 2 )~about 200g / (h·m 2 ), about 150g / (h·m 2 )~about 225g / (h·m 2 ), about 150g / (h·m 2 )~about 250g / (h·m 2 ), about 150g / (h·m 2 )~about 275g / (h·m 2 ), about 150g / (h·m 2 )~about 300g / (h·m 2 ), about 175g / (h·m 2 )~about 200g / (h·m 2 ), about 175g / (h·m 2 )~about 225g / (h·m 2 ), about 175g / (h·m 2 )~about 250g / (h·m 2 ), about 175g / (h·m 2 )~about 275g / (h·m 2 ), about 175g / (h·m 2 )~about 300g / (h·m 2 ), about 200g / (h·m 2 )~about 225g / (h·m 2 ), about 200g / (h·m 2 )~about 250g / (h·m 2 ), about 200g / (h·m 2 )~about 275g / (h·m 2 ), about 200g / (h·m 2 )~about 300g / (h·m 2 ), about 225g / (h·m 2 )~about 250g / (h·m 2 ), about 225g / (h·m2 ) ~ approx. 275g / (h m 2 ), approx. 225g / (h m 2 ) ~ approx. 300g / (h m 2 ), approx. 250g / (h m 2 ) ~ approx. 275g / (h m 2 ), approx. 250g / (h m 2 ) ~ approx. 300g / (h m 2 ), or approximately 275g / (h m 2 ) ~ approx. 300g / (h m 2 ) of GO material per area of the first filter. In some embodiments, the method of the first aspect can produce a throughput of about 100 g / (h m 2 ), approx. 125g / (h m 2 ), approx. 150g / (h m 2 ), approx. 175g / (h m 2 ), approx. 200g / (h m 2 ), approx. 225g / (h m 2 ), approx. 250g / (h m 2 ), approx. 275g / (h m 2 ), or approximately 300 g / (h m 2 ) of GO material per area of the first filter. In some embodiments, the method of the first aspect can produce a throughput of at least about 100 g / (h m 2 ), at least about 125g / (h m 2 ), at least about 150g / (h m 2 ), at least about 175g / (h m 2 ), at least about 200g / (h m 2 ), at least about 225g / (h m 2 ), at least about 250g / (h m 2 ), at least about 275g / (h m 2 ), or at least about 300 g / (h m 2 ) of GO material per area of the first filter. In some embodiments, the method of the first aspect can produce a throughput of GO material per area of the first filter of up to about 100 g / (h m 2 ), up to approx. 125g / (h m 2 ), up to about 150g / (h m2 ), up to approx. 175g / (h m 2 ), up to about 200g / (h m 2 ), up to approx. 225g / (h m 2 ), up to about 250g / (h m 2 ), up to approx. 275g / (h m 2 ), or up to about 300 g / (h m 2 ) of GO material per area of the first filter can be produced.
[0033] A second aspect provided herein is a method of forming a purified GO material, comprising adding a solvent solution to a GO suspension containing GO and filtering the GO solution through a first filter. In some embodiments, the GO suspension is formed by the Hummers process.
[0034] In some embodiments, the weight percent of GO in the GO suspension is about 0.05% to about 2%. In some embodiments, the weight percent of GO in the GO suspension is at least about 0.05%. In some embodiments, the weight percent of GO in the GO suspension is up to about 2%. In some embodiments, the weight percent of GO in the GO suspension is about 0.05% to about 0.1%, about 0.05% to about 0.2%, about 0.05% to about 0.4%, about 0.05% to about 0.6%, about 0.05% to about 0.8%, about 0.05% to about 1%, about 0.05% to about 1.2%, about 0.05% to about 1.4%, about 0.05% to about 1.6%, about 0.05% to about 1.8%, about 0.05% to about 2%, about 0.1% to about 0.2%, about 0.1% to about 0.4%, about 0.1% ~ about 0.6%, about 0.1% to about 0.8%, about 0.1% to about 1%, about 0.1% to about 1.2%, about 0.1% to about 1.4%, about 0.1% to about 1.6%, about 0.1% to about 1.8%, about 0.1% to about 2%, about 0.2% to about 0.4%, about 0.2% to about 0.6%, about 0.2% to about 0.8%, about 0.2% to about 1%, about 0.2% to about 1.2%, about 0.2% to about 1.4%, about 0.2% to about 1.6%, about 0.2% to about 1.8%, about 0.2% to about 2%, about 0.4% to about 0 .6%, about 0.4% to about 0.8%, about 0.4% to about 1%, about 0.4% to about 1.2%, about 0.4% to about 1.4%, about 0.4% to about 1.6%, about 0.4% to about 1.8%, about 0.4% to about 2%, about 0.6% to about 0.8%, about 0.6% to about 1%, about 0.6% to about 1.2%, about 0.6% to about 1.4%, about 0.6% to about 1.6%, about 0.6% to about 1.8%, about 0.6% to about 2%, about 0.8% to about 1%, about 0.8% to about 1.2%, about 0.8% to about 1.4%, about 0.8% to about 1.6%, about 0.8% to about 1.8%, about 0.8% to about 2%, about 1% to about 1.2%, about 1% to about 1.4%, about 1% to about 1.6%, about 1% to about 1.8%, about 1% to about 2%, about 1.2% to about 1.4%, about 1.2% to about 1.6%, about 1.2% to about 1.8%, about 1.2% to about 2%, about 1.4% to about 1.6%, about 1.4% to about 1.8%, about 1.4% to about 2%, about 1.6% to about 1.8%, about 1.6% to about 2%, or about 1.8% to about 2%.In some embodiments, the mass percentage of GO in the GO suspension is about 0.05%, about 0.1%, about 0.2%, about 0.4%, about 0.6%, about 0.8%, about 1%, about 1.2%, about 1.4%, about 1.6%, about 1.8%, or about 2%. In some embodiments, the mass percentage of GO in the GO suspension is at least about 0.05%, at least about 0.1%, at least about 0.2%, at least about 0.4%, at least about 0.6%, at least about 0.8%, at least about 1%, at least about 1.2%, at least about 1.4%, at least about 1.6%, at least about 1.8%, or at least about 2%. In some embodiments, the weight percentage of GO in the GO suspension is at most about 0.05%, at most about 0.1%, at most about 0.2%, at most about 0.4%, at most about 0.6%, at most about 0.8%, at most about 1%, at most about 1.2%, at most about 1.4%, at most about 1.6%, at most about 1.8%, or at most about 2%.
[0035] In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is about 10% to about 50%. In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is at least about 10%. In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is up to about 50%. In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is about 10% to about 15%, about 10% to about 20%, about 10% to about 25%, about 10% to about 30%, about 10% to about 35%, about 10% to about 40%, about 10% to about 45%, about 10% to about 50%, about 15% to about 20%, about 15% to about 25%, about 15% to about 30%, about 15% to about 35%, about 15% to about 40%, about 15% to about 45%, about 15% to about 50%, about 20% to about 25%, about 20% to about 30%, about 20% to about 35%, about 20% to about 40%, about 20% to about 45%, about 20% to about 50 ... 0% to about 30%, about 20% to about 35%, about 20% to about 40%, about 20% to about 45%, about 20% to about 50%, about 25% to about 30%, about 25% to about 35%, about 25% to about 40%, about 25% to about 45%, about 25% to about 50%, about 30% to about 35%, about 30% to about 40%, about 30% to about 45%, about 30% to about 50%, about 35% to about 40%, about 35% to about 45%, about 35% to about 50%, about 40% to about 45%, about 40% to about 50%, or about 45% to about 50%. In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, or about 50%. In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is at least about 10%, at least about 15%, at least about 20%, at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, or at least about 50%. In some embodiments, the weight percentage of the GO suspension in the GO suspension and solvent solution is at most about 10%, at most about 15%, at most about 20%, at most about 25%, at most about 30%, at most about 35%, at most about 40%, at most about 45%, or at most about 50%.
[0036] In some embodiments, the solvent solution comprises water, a solvent, or any combination thereof. In some embodiments, the solvent comprises an organic solvent. In some embodiments, the solvent The solvent may include acetic acid, acetone, acetonitrile, benzene, 1-butanol, 2-butanol, 2-butanone, t-butyl alcohol, carbon tetrachloride, chlorobenzene, chloroform, cyclohexane, 1,2-dichloroethane, diethylene glycol, diethyl ether, diglyme, diethylene glycol, dimethyl ether, 1,2-dimethoxyethane, dimethylformamide, dimethylsulfoxide, 1,4-dioxane, ethanol, ethyl acetate, ethylene glycol, glycerin, heptane, hexamethylphosphoramide, hexamethylphosphite triamide, hexane, methanol, methyl t-butyl ether, methylene chloride, N-methyl-2-pyrrolidinone, nitromethane, pentane, petroleum ether, 1-propanol, 2-propanol, pyridine, tetrahydrofuran, toluene, triethylamine, o-xylene, m-xylene, p-xylene, or any combination thereof. In some embodiments, the organic solvent comprises a polar organic solvent. In some embodiments, the polar organic solvent comprises ethyl acetate, tetrahydrofuran, dichloromethane, acetone, acetonitrile, dimethylformamide, dimethylsulfoxide, acetic acid, n-butanol, isopropanol, n-propanol, ethanol, methanol, formic acid, or any combination thereof. In some embodiments, the polar organic solvent comprises a protic polar organic solvent. In some embodiments, the protic polar organic solvent comprises acetic acid, n-butanol, isopropanol, n-propanol, ethanol, methanol, formic acid, or any combination thereof. In some embodiments, the polar organic solvent comprises an alcohol.In some embodiments, the alcohol comprises methanol, ethanol, propan-2-ol, butan-1-ol, pentan-1-ol, hexadecan-1-ol, ethane-1,2-diol, propane-1,2-diol, propane-1,2,3-triol, butane-1,2,3,4-tetraol, pentane-1,2,3,4,5-pentol, hexane-1,2,3,4,5,6-hexol, heptane-1,2,3,4,5,6,7-heptol, prop-2-en-1-ol, 3,7-dimethylocta-2,6-dien-1-ol, prop-2-yn-1-ol, cyclohexane-1,2,3,4,5,6-hexol, 2-(2-propyl)-5-methyl-cyclohexan-1-ol, or any combination thereof. In some embodiments, the solvent comprises methanol, ethanol, acetone, dimethylsulfoxide, dimethylformamide, N-methyl-2-pyrrolidone, or any combination thereof.
[0037] In some embodiments, the solvent has a vapor pressure of about 0.05 kPa to about 30 kPa. In some embodiments, the solvent has a vapor pressure of at least about 0.05 kPa. In some embodiments, the solvent has a vapor pressure of at most about 30 kPa. In some embodiments, the solvent has a vapor pressure of about 0.05 kPa to about 0.1 kPa, about 0.05 kPa to about 1 kPa, about 0.05 kPa to about 3 kPa, about 0.05 kPa to about 6 kPa, about 0.05 kPa to about 9 kPa, about 0.05 kPa to about 15 kPa, about 0.05 kPa to about 20 kPa, about 0.05 kPa to about 25 kPa, about 0.05 kPa to about 30 kPa, about 0.1 kPa, Pa to about 1 kPa, about 0.1 kPa to about 3 kPa, about 0.1 kPa to about 6 kPa, about 0.1 kPa to about 9 kPa, about 0.1 kPa to about 15 kPa, about 0.1 kPa to about 20 kPa, about 0.1 kPa to about 25 kPa, about 0.1 kPa to about 30 kPa, about 1 kPa to about 3 kPa, about 1 kPa to about 6 kPa, about 1 kPa to about 9 kPa, about 1 kPa to about 15 kPa, about 1 kPa to about 20kPa, about 1kPa to about 25kPa, about 1kPa to about 30kPa, about 3kPa to about 6kPa, about 3kPa to about 9kPa, about 3kPa to about 15kPa, about 3kPa to about 20kPa, about 3kPa to about 25kPa, about 3kPa to about 30kPa, about 6kPa to about 9kPa, about 6kPa to about 15kPa, about 6kPa to about 20kPa, about 6kPa to about 25kPa a, about 6 kPa to about 30 kPa, about 9 kPa to about 15 kPa, about 9 kPa to about 20 kPa, about 9 kPa to about 25 kPa, about 9 kPa to about 30 kPa, about 15 kPa to about 20 kPa, about 15 kPa to about 25 kPa, about 15 kPa to about 30 kPa, about 20 kPa to about 25 kPa, about 20 kPa to about 30 kPa, or about 25 kPa to about 30 kPa. In some embodiments, the solvent has a vapor pressure of about 0.05 kPa, about 0.1 kPa, about 1 kPa, about 3 kPa, about 6 kPa, about 9 kPa, about 15 kPa, about 20 kPa, about 25 kPa, or about 30 kPa.In some embodiments, the solvent has a vapor pressure of at least about 0.05 kPa, at least about 0.1 kPa, at least about 1 kPa, at least about 3 kPa, at least about 6 kPa, at least about 9 kPa, at least about 15 kPa, at least about 20 kPa, at least about 25 kPa, or at least about 30 kPa. In some embodiments, the solvent has a vapor pressure of at most about 0.05 kPa, at most about 0.1 kPa, at most about 1 kPa, at most about 3 kPa, at most about 6 kPa, at most about 9 kPa, at most about 15 kPa, at most about 20 kPa, at most about 25 kPa, or at most about 30 kPa.
[0038] In some embodiments, the weight percent of the solvent in the solvent solution is about 0.1% to about 99%. In some embodiments, the weight percent of the solvent in the solvent solution is at least about 0.1%. In some embodiments, the weight percent of the solvent in the solvent solution is up to about 99%. In some embodiments, the weight percent of the solvent in the solvent solution is about 0.1% to about 1%, about 0.1% to about 5%, about 0.1% to about 10%, about 0.1% to about 15%, about 0.1% to about 20%, about 0.1% to about 30%, about 0.1% to about 40%, about 0.1% to about 50%, about 0.1% to about 60%, about 0.1% to about 80%, about 0.1% to about 99%, about 1% to about 5%, about 1% to about 10%, about 1% to about 15%, about 1% to about 20%, about 1% to about 30%, about 1% to about 40%, about 1% to about 50%, about 1% to about 60%, about 1% to about 80%, about 1% to about 99%, about 5% to about 10%, about 5% to about 15%, about 5% to about 20%, about 5% to about 30%, about 5% to about 40%, about 5% to about 50%, about 5% to about 60%, about 5% to about 80%, about 5% to about 99%, about 10% to about 15%, about 10% to about 20%, about 10 % to about 30%, about 10% to about 40%, about 10% to about 50%, about 10% to about 60%, about 10% to about 80%, about 10% to about 99%, about 15% to about 20%, about 15% to about 30%, about 15% to about 40%, about 15% to about 50%, about 15% to about 60%, about 15% to about 80%, about 15% to about 99%, about 20% to about 30%, about 20% to about 40%, about 20% to about 50%, about 20% to about 60%, about 20% about 80%, about 20% to about 99%, about 30% to about 40%, about 30% to about 50%, about 30% to about 60%, about 30% to about 80%, about 30% to about 99%, about 40% to about 50%, about 40% to about 60%, about 40% to about 80%, about 40% to about 99%, about 50% to about 60%, about 50% to about 80%, about 50% to about 99%, about 60% to about 80%, about 60% to about 99%, or about 80% to about 99%. In some embodiments, the mass percentage of the solvent in the solvent solution is about 0.1%, about 1%, about 5%, about 10%, about 15%, about 20%, about 30%, about 40%, about 50%, about 60%, about 80%, or about 99%.In some embodiments, the weight percent of the solvent in the solvent solution is at least about 0.1%, at least about 1%, at least about 5%, at least about 10%, at least about 15%, at least about 20%, at least about 30%, at least about 40%, at least about 50%, at least about 60%, at least about 80%, or at least about 99%. In some embodiments, the weight percent of the solvent in the solvent solution is up to about 0.1%, up to about 1%, up to about 5%, up to about 10%, up to about 15%, up to about 20%, up to about 30%, up to about 40%, up to about 50%, up to about 60%, up to about 80%, or up to about 99%.
[0039] In some embodiments, filtering the GO solution comprises centrifugal filtration, dead-end filtration, cross-flow filtration, stationary phase filtration, dynamic phase filtration, surface filtration, depth filtration, vacuum filtration, recirculation filtration, or any combination thereof. In some embodiments, the first filter comprises a Büchner funnel, a surface filter, a sieve, a filter paper, a belt filter, a drum filter, a cross-flow filter, a screen filter, a depth filter, a polymeric membrane, a ceramic membrane, a stainless steel filter, a stainless steel mesh, a carbon fiber mesh, a microfilter, an ultrafiltration filter, a membrane, or any combination thereof.
[0040] In some embodiments, the first filter has a pore size of about 0.5 μm to about 100 μm. In some embodiments, the first filter has a pore size of at least about 0.5 μm. In some embodiments, the first filter has a pore size of at most about 100 μm. In some embodiments, the first filter has a pore size of at least about 0.5 μm to about 1 μm, about 0.5 μm to about 2 μm, about 0.5 μm to about 5 μm, about 0.5 μm to about 10 μm, about 0.5 μm to about 20 μm, about 0.5 μm to about 30 μm, about 0.5 μm to about 40 μm, about 0.5 μm to about 50 μm, about 0.5 μm to about 60 μm, about 0.5 μm to about 80 μm, about 0.5 μm to about 100 μm, about 1 μm to about 2 μm, about 1 μm to about 5 μm, about 1 μm to about 10 μm, about 1 μm to about 20 μm. m, about 1 μm to about 30 μm, about 1 μm to about 40 μm, about 1 μm to about 50 μm, about 1 μm to about 60 μm, about 1 μm to about 80 μm, about 1 μm to about 100 μm, about 2 μm to about 5 μm, about 2 μm to about 10 μm, about 2 μm to about 20 μm, Approximately 2 μm to approximately 30 μm, approximately 2 μm to approximately 40 μm, approximately 2 μm to approximately 50 μm, approximately 2 μm to approximately 60 μm, approximately 2 μm to approximately 80 μm, approximately 2 μm to approximately 100 μm, approximately 5 μm to approximately 10 μm, approximately 5 μm to approximately 20 μm, approximately 5 μm to approximately 30 μm, approximately 5 5μm to 50μm, 5μm to 60μm, 5μm to 80μm, 5μm to 100μm, 10μm to 20μm, 10μm to 30μm, 10μm to 40μm, 10μm to 50μm , about 10 μm to about 60 μm, about 10 μm to about 80 μm, about 10 μm to about 100 μm, about 20 μm to about 30 μm, about 20 μm to about 40 μm, about 20 μm to about 50 μm, about 20 μm to about 60 μm, about 20 μm to about 80 μm, about 20 μm The pore size is from about 30 μm to about 100 μm, from about 30 μm to about 40 μm, from about 30 μm to about 50 μm, from about 30 μm to about 60 μm, from about 30 μm to about 80 μm, from about 30 μm to about 100 μm, from about 40 μm to about 50 μm, from about 40 μm to about 60 μm, from about 40 μm to about 80 μm, from about 40 μm to about 100 μm, from about 50 μm to about 60 μm, from about 50 μm to about 80 μm, from about 50 μm to about 100 μm, from about 60 μm to about 80 μm, from about 60 μm to about 100 μm, or from about 80 μm to about 100 μm. In some embodiments, the first filter has a pore size of about 0.5 μm, about 1 μm, about 2 μm, about 5 μm, about 10 μm, about 20 μm, about 30 μm, about 40 μm, about 50 μm, about 60 μm, about 80 μm, or about 100 μm.In some embodiments, the first filter has a pore size of at least about 0.5 μm, at least about 1 μm, at least about 2 μm, at least about 5 μm, at least about 10 μm, at least about 20 μm, at least about 30 μm, at least about 40 μm, at least about 50 μm, at least about 60 μm, at least about 80 μm, or at least about 100 μm. In some embodiments, the first filter has a pore size of at most about 0.5 μm, at most about 1 μm, at most about 2 μm, at most about 5 μm, at most about 10 μm, at most about 20 μm, at most about 30 μm, at most about 40 μm, at most about 50 μm, at most about 60 μm, at most about 80 μm, or at most about 100 μm.
[0041] In some embodiments, the volumetric flux of the GO suspension and solvent solution through the first filter is about 10 liters per hour squared (L / (h m 2 ))~Approx. 100L / (h m 2 In some embodiments, the volumetric flux of the GO suspension and solvent solution through the first filter is at least about 10 L / (h m 2 In some embodiments, the volumetric flux of the GO suspension and solvent solution through the first filter is at most about 100 L / (h m 2 In some embodiments, the volumetric flux of the GO suspension and solvent solution through the first filter is about 10 L / (h m 2 ) ~ approx. 20L / (h m 2 ), approx. 10L / (h m 2 ) ~ approx. 30L / (h m 2 ), approx. 10L / (h m 2 ) ~ approx. 40L / (h m 2 ), approx. 10L / (h m 2 ) ~ approx. 50L / (h m 2 ), approx. 10L / (h m 2 ) ~ approx. 60L / (h m 2 ), approx. 10L / (h m 2 ) ~ approx. 70L / (h m 2 ), approx. 10L / (h m 2 ) ~ approx. 80L / (h m 2 ), approx. 10L / (h m 2)~about 90L / (h·m 2 ), about 10L / (h·m 2 )~about 100L / (h·m 2 ), about 20L / (h·m 2 )~about 30L / (h·m 2 ), about 20L / (h·m 2 )~about 40L / (h·m 2 ), about 20L / (h·m 2 )~about 50L / (h·m 2 ), about 20L / (h·m 2 )~about 60L / (h·m 2 ), about 20L / (h·m 2 )~about 70L / (h·m 2 ), about 20L / (h·m 2 )~about 80L / (h·m 2 ), about 20L / (h·m 2 )~about 90L / (h·m 2 ), about 20L / (h·m 2 )~about 100L / (h·m 2 ), about 30L / (h·m 2 )~about 40L / (h·m 2 ), about 30L / (h·m 2 )~about 50L / (h·m 2 ), about 30L / (h·m 2 )~about 60L / (h·m 2 ), about 30L / (h·m 2 )~about 70L / (h·m 2 ), about 30L / (h·m 2 )~about 80L / (h·m 2 ), about 30L / (h·m 2 )~about 90L / (h·m 2 ), about 30L / (h·m 2 )~about 100L / (h·m 2 ), about 40L / (h·m 2 )~about 50L / (h·m 2 ), about 40L / (h·m 2 )~about 60L / (h·m 2 ), about 40L / (h·m 2 )~about 70L / (h·m 2 ), about 40L / (h·m 2 )~about 80L / (h·m 2 ), about 40L / (h·m2 ) ~ approx. 90L / (h m 2 ), approx. 40L / (h m 2 ) ~ approx. 100L / (h m 2 ), approx. 50L / (h m 2 ) ~ approx. 60L / (h m 2 ), approx. 50L / (h m 2 ) ~ approx. 70L / (h m 2 ), approx. 50L / (h m 2 ) ~ approx. 80L / (h m 2 ), approx. 50L / (h m 2 ) ~ approx. 90L / (h m 2 ), approx. 50L / (h m 2 ) ~ approx. 100L / (h m 2 ), approx. 60L / (h m 2 ) ~ approx. 70L / (h m 2 ), approx. 60L / (h m 2 ) ~ approx. 80L / (h m 2 ), approx. 60L / (h m 2 ) ~ approx. 90L / (h m 2 ), approx. 60L / (h m 2 ) ~ approx. 100L / (h m 2 ), approx. 70L / (h m 2 ) ~ approx. 80L / (h m 2 ), approx. 70L / (h m 2 ) ~ approx. 90L / (h m 2 ), approx. 70L / (h m 2 ) ~ approx. 100L / (h m 2 ), approx. 80L / (h m 2 ) ~ approx. 90L / (h m 2 ), approx. 80L / (h m 2 ) ~ approx. 100L / (h m 2 ), or approximately 90 L / (h m 2 ) ~ approx. 100L / (h m 2 In some embodiments, the volumetric flux of the GO suspension and solvent solution through the first filter is about 10 L / (h m 2 ), approx. 20L / (h m 2 ), approx. 30L / (h m 2 ), approx. 40L / (h m 2 ), approx. 50L / (h m 2 ), approx. 60L / (h m 2), approx. 70L / (h m 2 ), approx. 80L / (h m 2 ), approx. 90L / (h m 2 ), or approximately 100 L / (h m 2 In some embodiments, the volumetric flux of the GO suspension and solvent solution through the first filter is at least about 10 L / (h m 2 ), at least about 20L / (h m 2 ), at least about 30L / (h m 2 ), at least about 40L / (h m 2 ), at least about 50L / (h m 2 ), at least about 60L / (h m 2 ), at least about 70L / (h m 2 ), at least about 80L / (h m 2 ), at least about 90L / (h m 2 ), or at least about 100 L / (h m 2 In some embodiments, the volumetric flux of the GO suspension and solvent solution through the first filter is at most about 10 L / (h m 2 ), maximum of approximately 20 L / (h m 2 ), maximum of approx. 30L / (h m 2 ), maximum of approx. 40L / (h m 2 ), up to approx. 50L / (h m 2 ), maximum of approximately 60L / (h m 2 ), maximum of approx. 70L / (h m 2 ), maximum of approximately 80L / (h m 2 ), maximum of approximately 90L / (h m 2 ), or up to about 100 L / (h m 2 ).
[0042] In some embodiments, filtering the GO solution includes cross-flow recirculation filtering the GO solution to form a retentate and a permeate, where the retentate is added to the GO solution. Some embodiments further include continuously adding a volume of a solvent solution to the GO solution during the cross-flow recirculation filtering of the GO solution. In some embodiments, the volume of solvent solution is added to the GO solution at a solvent solution flow rate that is approximately the same as the permeate flow rate.
[0043] In some embodiments, the solvent solution comprises water for a period of time. In some embodiments, the solvent solution comprises a solvent for a period of time. In some embodiments, the solvent solution comprises water and a solvent for a period of time. In some embodiments, the solvent comprises an organic solvent. In some embodiments, the solvent solution comprises at least one of water and a solvent for a period of time.
[0044] Some embodiments further include dehydrating the GO suspension, hi some embodiments, the GO suspension is dehydrated using a second filter prior to depositing the GO suspension and solvent solution onto the first filter.
[0045] In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by about 45% to about 99%. In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by at least about 45%. In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by up to about 99%. In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by about 45% to about 50%, about 45% to about 55%, about 45% to about 60%, about 45% to about 65%, about 45% to about 70%, about 45% to about 75%, about 45% to about 80%, about 45% to about 85%, about 45% to about 90%, about 45% to about 99%, about 50% to about 55%. , about 50% to about 60%, about 50% to about 65%, about 50% to about 70%, about 50% to about 75%, about 50% to about 80%, about 50% to about 85%, about 50% to about 90%, about 50% to about 99%, about 55% to about 60%, about 55% to about 65%, about 55% to about 70%, about 55% to about 75%, about 55% to about 80%, about 55% to about 85%, about 55% to about 90% , about 55% to about 99%, about 60% to about 65%, about 60% to about 70%, about 60% to about 75%, about 60% to about 80%, about 60% to about 85%, about 60% to about 90%, about 60% to about 99%, about 65% to about 70%, about 65% to about 75%, about 65% to about 80%, about 65% to about 85%, about 65% to about 90%, about 65% to about 99%, about 70% to about 75% , about 70% to about 80%, about 70% to about 85%, about 70% to about 90%, about 70% to about 99%, about 75% to about 80%, about 75% to about 85%, about 75% to about 90%, about 75% to about 99%, about 80% to about 85%, about 80% to about 90%, about 80% to about 99%, about 85% to about 90%, about 85% to about 99%, or about 90% to about 99%. In some embodiments, by dehydrating the GO suspension, the water content of the GO suspension is reduced by about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, about 90%, or about 99%.In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by at least about 45%, at least about 50%, at least about 55%, at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, at least about 85%, at least about 90%, or at least about 99%. In some embodiments, dehydrating the GO suspension reduces the water content of the GO suspension by up to about 45%, up to about 50%, up to about 55%, up to about 60%, up to about 65%, up to about 70%, up to about 75%, up to about 80%, up to about 85%, up to about 90%, or up to about 99%.
[0046] In some embodiments, dehydrating the GO suspension is performed immediately prior to adding the solvent solution to the GO suspension.
[0047] In some embodiments, dewatering the GO suspension comprises centrifugal filtration, dead-end filtration, cross-flow filtration, stationary phase filtration, dynamic phase filtration, surface filtration, depth filtration, vacuum filtration, recirculation filtration, or any combination thereof. In some embodiments, the second filter comprises a Büchner funnel, a surface filter, a sieve, a filter paper, a belt filter, a drum filter, a cross-flow filter, a screen filter, a depth filter, a polymeric membrane, a ceramic membrane, a stainless steel filter, a stainless steel mesh, a carbon fiber mesh, a microfilter, an ultrafiltration filter, or any combination thereof.
[0048] In some embodiments, the second filter has a pore size of about 0.5 μm to about 100 μm. In some embodiments, the second filter has a pore size of at least about 0.5 μm. In some embodiments, the second filter has a pore size of at most about 100 μm. In some embodiments, the second filter has a thickness of about 0.5 μm to about 1 μm, about 0.5 μm to about 2 μm, about 0.5 μm to about 5 μm, about 0.5 μm to about 10 μm, about 0.5 μm to about 20 μm, about 0.5 μm to about 30 μm, about 0.5 μm to about 40 μm, about 0.5 μm to about 50 μm, about 0.5 μm to about 60 μm, about 0.5 μm to about 80 μm, about 0.5 μm to about 100 μm, about 1 μm to about 2 μm, about 1 μm to about 5 μm, about 1 μm to about 10 μm, or about 1 μm to about 20 μm. m, about 1 μm to about 30 μm, about 1 μm to about 40 μm, about 1 μm to about 50 μm, about 1 μm to about 60 μm, about 1 μm to about 80 μm, about 1 μm to about 100 μm, about 2 μm to about 5 μm, about 2 μm to about 10 μm, about 2 μm to about 20 μm, Approximately 2 μm to approximately 30 μm, approximately 2 μm to approximately 40 μm, approximately 2 μm to approximately 50 μm, approximately 2 μm to approximately 60 μm, approximately 2 μm to approximately 80 μm, approximately 2 μm to approximately 100 μm, approximately 5 μm to approximately 10 μm, approximately 5 μm to approximately 20 μm, approximately 5 μm to approximately 30 μm, approximately 5 5μm to 50μm, 5μm to 60μm, 5μm to 80μm, 5μm to 100μm, 10μm to 20μm, 10μm to 30μm, 10μm to 40μm, 10μm to 50μm , about 10 μm to about 60 μm, about 10 μm to about 80 μm, about 10 μm to about 100 μm, about 20 μm to about 30 μm, about 20 μm to about 40 μm, about 20 μm to about 50 μm, about 20 μm to about 60 μm, about 20 μm to about 80 μm, about 20 μm The pore size is from about 30 μm to about 100 μm, from about 30 μm to about 40 μm, from about 30 μm to about 50 μm, from about 30 μm to about 60 μm, from about 30 μm to about 80 μm, from about 30 μm to about 100 μm, from about 40 μm to about 50 μm, from about 40 μm to about 60 μm, from about 40 μm to about 80 μm, from about 40 μm to about 100 μm, from about 50 μm to about 60 μm, from about 50 μm to about 80 μm, from about 50 μm to about 100 μm, from about 60 μm to about 80 μm, from about 60 μm to about 100 μm, or from about 80 μm to about 100 μm.In some embodiments, the second filter has a pore size of about 0.5 μm, about 1 μm, about 2 μm, about 5 μm, about 10 μm, about 20 μm, about 30 μm, about 40 μm, about 50 μm, about 60 μm, about 80 μm, or about 100 μm. In some embodiments, the second filter has a pore size of at least about 0.5 μm, at least about 1 μm, at least about 2 μm, at least about 5 μm, at least about 10 μm, at least about 20 μm, at least about 30 μm, at least about 40 μm, at least about 50 μm, at least about 60 μm, at least about 80 μm, or at least about 100 μm. In some embodiments, the second filter has a pore size of at most about 0.5 μm, at most about 1 μm, at most about 2 μm, at most about 5 μm, at most about 10 μm, at most about 20 μm, at most about 30 μm, at most about 40 μm, at most about 50 μm, at most about 60 μm, at most about 80 μm, or at most about 100 μm.
[0049] In some embodiments, the second filter is the first filter. In some embodiments, the second filter and the first filter are separate filters.
[0050] In some embodiments, the mass percent of GO in the GO suspension after filtering the GO solution through a second filter is about 0.1 L / (h m 2 ) ~ approx. 1L / (h m 2 In some embodiments, the mass percent of GO in the GO suspension after filtering the GO solution through a second filter is at least about 0.1 L / (h m 2 In some embodiments, the mass percent of GO in the GO suspension after filtering the GO solution through a second filter is at most about 1 L / (h m 2 In some embodiments, the mass percent of GO in the GO suspension after filtering the GO solution through a second filter is about 0.1 L / (h m 2 ) ~ approx. 0.2L / (h m 2 ), approx. 0.1L / (h m 2 ) ~ approx. 0.3L / (h m 2), about 0.1L / (h·m 2 )~about 0.4L / (h·m 2 ), about 0.1L / (h·m 2 )~about 0.5L / (h·m 2 ), about 0.1L / (h·m 2 )~about 0.6L / (h·m 2 ), about 0.1L / (h·m 2 )~about 0.7L / (h·m 2 ), about 0.1L / (h·m 2 )~about 0.8L / (h·m 2 ), about 0.1L / (h·m 2 )~about 0.9L / (h·m 2 ), about 0.1L / (h·m 2 )~about 1L / (h·m 2 ), about 0.2L / (h·m 2 )~about 0.3L / (h·m 2 ), about 0.2L / (h·m 2 )~about 0.4L / (h·m 2 ), about 0.2L / (h·m 2 )~about 0.5L / (h·m 2 ), about 0.2L / (h·m 2 )~about 0.6L / (h·m 2 ), about 0.2L / (h·m 2 )~about 0.7L / (h·m 2 ), about 0.2L / (h·m 2 )~about 0.8L / (h·m 2 ), about 0.2L / (h·m 2 )~about 0.9L / (h·m 2 ), about 0.2L / (h·m 2 )~about 1L / (h·m 2 ), about 0.3L / (h·m 2 )~about 0.4L / (h·m 2 ), about 0.3L / (h·m 2 )~about 0.5L / (h·m 2 ), about 0.3L / (h·m 2 )~about 0.6L / (h·m 2 ), about 0.3L / (h·m 2 )~about 0.7L / (h·m 2 ), about 0.3L / (h·m 2 )~about 0.8L / (h·m 2), about 0.3L / (h·m 2 )~about 0.9L / (h·m 2 ), about 0.3L / (h·m 2 )~about 1L / (h·m 2 ), about 0.4L / (h·m 2 )~about 0.5L / (h·m 2 ), about 0.4L / (h·m 2 )~about 0.6L / (h·m 2 ), about 0.4L / (h·m 2 )~about 0.7L / (h·m 2 ), about 0.4L / (h·m 2 )~about 0.8L / (h·m 2 ), about 0.4L / (h·m 2 )~about 0.9L / (h·m 2 ), about 0.4L / (h·m 2 )~about 1L / (h·m 2 ), about 0.5L / (h·m 2 )~about 0.6L / (h·m 2 ), about 0.5L / (h·m 2 )~about 0.7L / (h·m 2 ), about 0.5L / (h·m 2 )~about 0.8L / (h·m 2 ), about 0.5L / (h·m 2 )~about 0.9L / (h·m 2 ), about 0.5L / (h·m 2 )~about 1L / (h·m 2 ), about 0.6L / (h·m 2 )~about 0.7L / (h·m 2 ), about 0.6L / (h·m 2 )~about 0.8L / (h·m 2 ), about 0.6L / (h·m 2 )~about 0.9L / (h·m 2 ), about 0.6L / (h·m 2 )~about 1L / (h·m 2 ), about 0.7L / (h·m 2 )~about 0.8L / (h·m 2 ), about 0.7L / (h·m 2 )~about 0.9L / (h·m 2 ), about 0.7L / (h·m 2 )~about 1L / (h·m 2), approx. 0.8L / (h m 2 ) ~ approx. 0.9L / (h m 2 ), approx. 0.8L / (h m 2 ) ~ approx. 1L / (h m 2 ), or approximately 0.9 L / (h m 2 ) ~ approx. 1L / (h m 2 In some embodiments, the mass percent of GO in the GO suspension after filtering the GO solution through a second filter is about 0.1 L / (h m 2 ), approx. 0.2L / (h m 2 ), approx. 0.3L / (h m 2 ), approx. 0.4L / (h m 2 ), approx. 0.5L / (h m 2 ), approx. 0.6L / (h m 2 ), approx. 0.7L / (h m 2 ), approx. 0.8L / (h m 2 ), approx. 0.9L / (h m 2 ), or approximately 1 L / (h m 2 ).
[0051] Some embodiments further include drying the GO suspension. In some embodiments, drying the GO suspension is performed by air blowing, dry evaporation, oven heating, freeze drying, or any combination thereof. In some embodiments, drying the GO suspension is performed by a drying method known to those skilled in the art. In some embodiments, dry evaporation is performed at ambient temperature. In some embodiments, air blowing is performed using a dry gas flow. In some embodiments, air blowing is performed using a dry gas flow at a pressure of about 10 psi to about 30 psi. In some embodiments, drying the GO suspension is performed for a period of at least about 5 minutes, at least 10 minutes, at least 20 minutes, at least 30 minutes, at least 40 minutes, at least 50 minutes, or at least about 60 minutes, and / or for a period of about 5 minutes or less, 10 minutes or less, 20 minutes or less, 30 minutes or less, 40 minutes or less, 50 minutes or less, or about 60 minutes or less. In some embodiments, drying the GO suspension is carried out for a period of at least about 1 hour, at least 2 hours, at least 3 hours, at least 4 hours, at least 5 hours, at least 6 hours, at least 7 hours, at least 8 hours, at least 9 hours, at least 10 hours, at least 11 hours, or at least about 12 hours, and / or for a period of about 1 hour or less, 2 hours or less, 3 hours or less, 4 hours or less, 5 hours or less, 6 hours or less, 7 hours or less, 8 hours or less, 9 hours or less, 10 hours or less, 11 hours or less, or about 12 hours or less.
[0052] In some embodiments, the heating is performed at a temperature of about 10° C. to about 50° C. In some embodiments, the heating is performed at a temperature of at least about 10° C. In some embodiments, the heating is performed at a temperature of up to about 50° C. In some embodiments, the heating is at about 10°C to about 15°C, about 10°C to about 20°C, about 10°C to about 25°C, about 10°C to about 30°C, about 10°C to about 35°C, about 10°C to about 40°C, about 10°C to about 45°C, about 10°C to about 50°C, about 15°C to about 20°C, about 15°C to about 25°C, about 15°C to about 30°C, about 15°C to about 35°C, about 15°C to about 40°C, about 15°C to about 45°C, about 15°C to about 50°C, about 20°C to about 25°C, about 20°C to about 30°C, about 20°C to about 35°C, about 20°C to about 40°C, about 20°C to about 45°C, about 20°C to about 50°C, about 25°C to about 30°C, about 25°C to about 35°C, about 25°C to about 40°C, The heating is carried out at a temperature of about 25°C to about 45°C, about 25°C to about 50°C, about 30°C to about 35°C, about 30°C to about 40°C, about 30°C to about 45°C, about 30°C to about 50°C, about 35°C to about 40°C, about 35°C to about 45°C, about 35°C to about 50°C, about 40°C to about 45°C, about 40°C to about 50°C, or about 45°C to about 50°C. In some embodiments, the heating is carried out at a temperature of about 10°C, about 15°C, about 20°C, about 25°C, about 30°C, about 35°C, about 40°C, about 45°C, or about 50°C. In some embodiments, the heating is carried out at a temperature of at least about 10°C, at least about 15°C, at least about 20°C, at least about 25°C, at least about 30°C, at least about 35°C, at least about 40°C, at least about 45°C, or at least about 50°C. In some embodiments, heating is carried out at a temperature of up to about 10°C, up to about 15°C, up to about 20°C, up to about 25°C, up to about 30°C, up to about 35°C, up to about 40°C, up to about 45°C, or up to about 50°C.
[0053] In some embodiments, the weight percent of GO in the GO suspension after drying the GO suspension is about 30% to about 90%. In some embodiments, the weight percent of GO in the GO suspension after drying the GO suspension is at least about 30%. In some embodiments, the weight percent of GO in the GO suspension after drying the GO suspension is up to about 90%. In some embodiments, the weight percent of GO in the GO suspension after drying the GO suspension is about 30% to about 35%, about 30% to about 40%, about 30% to about 45%, about 30% to about 50%, about 30% to about 55%, about 30% to about 60%, about 30% to about 65%, about 30% to about 70%, about 30% to about 75%, about 30% to about 80%, about 30% to about 90%, about 35% to about 40%, about 35% to about 45%, about 35% to about 5 ... 5% to about 50%, about 35% to about 55%, about 35% to about 60%, about 35% to about 65%, about 35% to about 70%, about 35% to about 75%, about 35% to about 80%, about 35% to about 90%, about 40% to about 45%, about 40% to about 50%, about 40% to about 55%, about 40% to about 60%, about 40% to about 65%, about 40% to about 70%, about 40% to about 75%, about 40% to about 80%, about 40% to about 90%, about 45% to about 50%, About 45% to about 55%, about 45% to about 60%, about 45% to about 65%, about 45% to about 70%, about 45% to about 75%, about 45% to about 80%, about 45% to about 90%, about 50% to about 55%, about 50% to about 60%, about 50% to about 65%, about 50% to about 70%, about 50% to about 75%, about 50% to about 80%, about 50% to about 90%, about 55% to about 60%, about 55% to about 65%, about 55% to about 70%, about 55% to about 75 %, about 55% to about 80%, about 55% to about 90%, about 60% to about 65%, about 60% to about 70%, about 60% to about 75%, about 60% to about 80%, about 60% to about 90%, about 65% to about 70%, about 65% to about 75%, about 65% to about 80%, about 65% to about 90%, about 70% to about 75%, about 70% to about 80%, about 70% to about 90%, about 75% to about 80%, about 75% to about 90%, or about 80% to about 90%. In some embodiments, after the GO suspension is dried, the mass percentage of GO in the GO suspension is about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, or about 90%.In some embodiments, the weight percent of GO in the GO suspension after drying is at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, at least about 55%, at least about 60%, at least about 65%, at least about 70%, at least about 75%, at least about 80%, or at least about 90%. In some embodiments, the weight percent of GO in the GO suspension after drying is at most about 30%, at most about 35%, at most about 40%, at most about 45%, at most about 50%, at most about 55%, at most about 60%, at most about 65%, at most about 70%, at most about 75%, at most about 80%, or at most about 90%.
[0054] In some embodiments, the GO powder is formed by drying the GO suspension. In some embodiments, the GO powder is dispersible in water or a polar solvent. In some embodiments, the GO powder is anhydrous, intercalated, exfoliated, or any combination thereof. In some embodiments, the GO powder comprises a single layer of GO. In some embodiments, the GO powder is dispersible in water, a polar solvent, or any combination thereof.
[0055] In some embodiments, the GO material is water-based, hi some embodiments, the water-based material comprises an ink, a paste, a solution, a fluid, a liquid, a paint, a dye, a coating, or a compound.
[0056] In some embodiments, the GO material has a viscosity of about 800 m 2 / g ~ approx. 2,400m 2 In some embodiments, the GO material has a surface area of at least about 800 m / g. 2 / g. In some embodiments, the GO material has a surface area of up to about 2,400 m 2 / g. In some embodiments, the GO material has a surface area of about 800 m 2 / g ~ approx. 1,000m 2 / g, approx. 800m 2 / g ~ approx. 1,200m2 / g, about 800m 2 / g~about 1,400m 2 / g, about 800m 2 / g~about 1,600m 2 / g, about 800m 2 / g~about 1,800m 2 / g, about 800m 2 / g~about 2,000m 2 / g, about 800m 2 / g~about 2,200m 2 / g, about 800m 2 / g~about 2,400m 2 / g, about 1,000m 2 / g~about 1,200m 2 / g, about 1,000m 2 / g~about 1,400m 2 / g, about 1,000m 2 / g~about 1,600m 2 / g, about 1,000m 2 / g~about 1,800m 2 / g, about 1,000m 2 / g~about 2,000m 2 / g, about 1,000m 2 / g~about 2,200m 2 / g, about 1,000m 2 / g~about 2,400m 2 / g, about 1,200m 2 / g~about 1,400m 2 / g, about 1,200m 2 / g~about 1,600m 2 / g, about 1,200m 2 / g~about 1,800m 2 / g, about 1,200m 2 / g~about 2,000m 2 / g, about 1,200m 2 / g~about 2,200m 2 / g, about 1,200m 2 / g~about 2,400m 2 / g, about 1,400m 2 / g~about 1,600m 2 / g, about 1,400m 2 / g~about 1,800m 2 / g, about 1,400m 2 / g~about 2,000m2 / g, approx. 1,400m 2 / g ~ approx. 2,200m 2 / g, approx. 1,400m 2 / g ~ approx. 2,400m 2 / g, approx. 1,600m 2 / g ~ approx. 1,800m 2 / g, approx. 1,600m 2 / g ~ approx. 2,000m 2 / g, approx. 1,600m 2 / g ~ approx. 2,200m 2 / g, approx. 1,600m 2 / g ~ approx. 2,400m 2 / g, approx. 1,800m 2 / g ~ approx. 2,000m 2 / g, approx. 1,800m 2 / g ~ approx. 2,200m 2 / g, approx. 1,800m 2 / g ~ approx. 2,400m 2 / g, approx. 2,000m 2 / g ~ approx. 2,200m 2 / g, approx. 2,000m 2 / g ~ approx. 2,400m 2 / g, or approximately 2,200 m 2 / g ~ approx. 2,400m 2 / g. In some embodiments, the GO material has a surface area of about 800 m 2 / g, approx. 1,000m 2 / g, approx. 1,200m 2 / g, approx. 1,400m 2 / g, approx. 1,600m 2 / g, approx. 1,800m 2 / g, approx. 2,000m 2 / g, approx. 2,200m 2 / g, or approximately 2,400 m 2 / g surface area.
[0057] In some embodiments, the GO material has a conductivity of about 0.1 S / m to about 5 S / m. In some embodiments, the GO material has a conductivity of at least about 0.1 S / m. In some embodiments, the GO material has a conductivity of up to about 5 S / m. In some embodiments, the GO material has a conductivity of about 0.1 S / m to about 0.2 S / m, about 0.1 S / m to about 0.5 S / m, about 0.1 S / m to about 0.75 S / m, about 0.1 S / m to about 1 S / m, about 0.1 S / m to about 2 S / m, about 0.1 S / m to about 3 S / m, about 0.1 S / m to about 4 S / m, about 0.1 S / m to about 5 S / m, about 0.2S / m to about 0.5S / m, about 0.2S / m to about 0.75S / m, about 0.2S / m to about 1S / m, about 0.2S / m to about 2S / m, about 0.2S / m~Approx. 3S / m, Approx. 0.2S / m~Approx. 4S / m, Approx. 0.2S / m~Approx. 5S / m, Approx. 0.5S / m~Approx. 0.75S / m, Approx. 0.5S / m~Approx. 1S / m, about 0.5S / m to about 2S / m, about 0.5S / m to about 3S / m, about 0.5S / m to about 4S / m, about 0.5S / m to about 5S / m, about 0.75 S / m ~ approx. 1S / m, approx. 0.75S / m ~ approx. 2S / m, approx. 0.75S / m ~ approx. 3S / m, approx. 0.75S / m ~ approx. 4S / m, approx. 0.75S / m ~ approx. 5S In some embodiments, the GO material has a conductivity of about 0.1 S / m, about 0.2 S / m, about 0.5 S / m, about 0.75 S / m, about 1 S / m, about 2 S / m, about 3 S / m, about 4 S / m, or about 5 S / m. In some embodiments, the GO material has a conductivity of at least about 0.1 S / m, at least about 0.2 S / m, at least about 0.5 S / m, at least about 0.75 S / m, at least about 1 S / m, at least about 2 S / m, at least about 3 S / m, at least about 4 S / m, or at least about 5 S / m. In some embodiments, the GO material has a conductivity of at most about 0.1 S / m, at most about 0.2 S / m, at most about 0.5 S / m, at most about 0.75 S / m, at most about 1 S / m, at most about 2 S / m, at most about 3 S / m, at most about 4 S / m, or at most about 5 S / m.
[0058] In some embodiments, the GO material has a C:O mass ratio of about 1:3 to about 5:1. In some embodiments, the GO material has a C:O mass ratio of at least about 1:3. In some embodiments, the GO material has a C:O mass ratio of up to about 5:1. In some embodiments, the GO material has a C:O mass ratio of about 1:3 to about 1:2, about 1:3 to about 1:1, about 1:3 to about 2:1, about 1:3 to about 3:1, about 1:3 to about 4:1, about 1:3 to about 5:1, about 1:2 to about 1:1, about 1:2 to about 2:1, about 1:2 to about 3:1, about 1:2 to about 4:1, about 1:2 to about 5:1, about 1:1 to about 2:1, about 1:1 to about 3:1, about 1:1 to about 4:1, about 1:1 to about 5:1, about 2:1 to about 3:1, about 2:1 to about 4:1, about 2:1 to about 5:1, about 3:1 to about 4:1, about 3:1 to about 5:1, or about 4:1 to about 5:1. In some embodiments, the GO material has a C:O mass ratio of about 1:3, about 1:2, about 1:1, about 2:1, about 3:1, about 4:1, or about 5:1. In some embodiments, the GO material has a C:O mass ratio of at least about 1:3, at least about 1:2, at least about 1:1, at least about 2:1, at least about 3:1, at least about 4:1, or at least about 5:1. In some embodiments, the GO material has a C:O mass ratio of up to about 1:3, up to about 1:2, up to about 1:1, up to about 2:1, up to about 3:1, up to about 4:1, or up to about 5:1.
[0059] In some embodiments, the GO material has an oxidation rate of about 15% to about 60%. In some embodiments, the GO material has an oxidation rate of at least about 15%. In some embodiments, the GO material has an oxidation rate of up to about 60%. In some embodiments, the GO material is about 15% to about 20%, about 15% to about 25%, about 15% to about 30%, about 15% to about 35%, about 15% to about 40%, about 15% to about 45%, about 15% to about 50%, about 15% to about 55%, about 15% to about 60%, about 20% to about 25%, about 20% to about 30%, about 20% to about 35%, about 20% to about 40%, about 20% to about 45%, about 20% to about 50%, about 20% to about 55%, about 20% to about 60%, about 25% to about 30%, about 25% to about 35%, about 25% to about 40%, about 25% to about 45%, about 25% to about 50%, about The oxidation rate is from about 25% to about 55%, from about 25% to about 60%, from about 30% to about 35%, from about 30% to about 40%, from about 30% to about 45%, from about 30% to about 50%, from about 30% to about 55%, from about 30% to about 60%, from about 35% to about 40%, from about 35% to about 45%, from about 35% to about 50%, from about 35% to about 55%, from about 35% to about 60%, from about 40% to about 45%, from about 40% to about 50%, from about 40% to about 55%, from about 40% to about 60%, from about 45% to about 50%, from about 45% to about 55%, from about 45% to about 60%, from about 50% to about 55%, from about 50% to about 60%, or from about 55% to about 60%. In some embodiments, the GO material has an oxidation rate of about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, or about 60%. In some embodiments, the GO material has an oxidation rate of at least about 15%, at least about 20%, at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, at least about 55%, or at least about 60%. In some embodiments, the GO material has an oxidation rate of up to about 15%, up to about 20%, up to about 25%, up to about 30%, up to about 35%, up to about 40%, up to about 45%, up to about 50%, up to about 55%, or up to about 60%.
[0060] In some embodiments, one of the electrical conductivity, surface area, C:O ratio, and oxidation rate of the GO material is measured by methylene blue absorption.
[0061] In some embodiments of this aspect, the method comprises a step of: 2 ) ~ approx. 100g / (h m 2 ) of GO material per area of the first filter. In some embodiments of this aspect, the method can produce a throughput of at least about 25 g / (h m 2 ) of GO material per area of the first filter. In some embodiments of this aspect, the method can produce a throughput of GO material of up to about 100 g / (h m 2 ) of GO material per area of the first filter. In some embodiments of this aspect, the method can produce a throughput of about 25 g / (h m 2 ) ~ approx. 30g / (h m 2 ), approx. 25g / (h m 2 ) ~ approx. 35g / (h m 2 ), approx. 25g / (h m 2 ) ~ approx. 40g / (h m 2 ), approx. 25g / (h m 2 ) ~ approx. 45g / (h m 2 ), approx. 25g / (h m 2 ) ~ approx. 50g / (h m 2 ), approx. 25g / (h m 2 ) ~ approx. 60g / (h m 2 ), approx. 25g / (h m 2 ) ~ approx. 70g / (h m 2 ), approx. 25g / (h m 2 ) ~ approx. 80g / (h m 2 ), approx. 25g / (h m 2 ) ~ approx. 90g / (h m 2 ), approx. 25g / (h m 2 ) ~ approx. 100g / (h m 2 ), approx. 30g / (h m 2 ) ~ approx. 35g / (h m 2 ), approx. 30g / (h m 2 ) ~ approx. 40g / (h m 2 ), approx. 30g / (h m2 )~about 45g / (h·m 2 ), about 30g / (h·m 2 )~about 50g / (h·m 2 ), about 30g / (h·m 2 )~about 60g / (h·m 2 ), about 30g / (h·m 2 )~about 70g / (h·m 2 ), about 30g / (h·m 2 )~about 80g / (h·m 2 ), about 30g / (h·m 2 )~about 90g / (h·m 2 ), about 30g / (h·m 2 )~about 100g / (h·m 2 ), about 35g / (h·m 2 )~about 40g / (h·m 2 ), about 35g / (h·m 2 )~about 45g / (h·m 2 ), about 35g / (h·m 2 )~about 50g / (h·m 2 ), about 35g / (h·m 2 )~about 60g / (h·m 2 ), about 35g / (h·m 2 )~about 70g / (h·m 2 ), about 35g / (h·m 2 )~about 80g / (h·m 2 ), about 35g / (h·m 2 )~about 90g / (h·m 2 ), about 35g / (h·m 2 )~about 100g / (h·m 2 ), about 40g / (h·m 2 )~about 45g / (h·m 2 ), about 40g / (h·m 2 )~about 50g / (h·m 2 ), about 40g / (h·m 2 )~about 60g / (h·m 2 ), about 40g / (h·m 2 )~about 70g / (h·m 2 ), about 40g / (h·m 2 )~about 80g / (h·m 2 ), about 40g / (h·m 2 )~about 90g / (h·m 2), about 40g / (h·m 2 )~about 100g / (h·m 2 ), about 45g / (h·m 2 )~about 50g / (h·m 2 ), about 45g / (h·m 2 )~about 60g / (h·m 2 ), about 45g / (h·m 2 )~about 70g / (h·m 2 ), about 45g / (h·m 2 )~about 80g / (h·m 2 ), about 45g / (h·m 2 )~about 90g / (h·m 2 ), about 45g / (h·m 2 )~about 100g / (h·m 2 ), about 50g / (h·m 2 )~about 60g / (h·m 2 ), about 50g / (h·m 2 )~about 70g / (h·m 2 ), about 50g / (h·m 2 )~about 80g / (h·m 2 ), about 50g / (h·m 2 )~about 90g / (h·m 2 ), about 50g / (h·m 2 )~about 100g / (h·m 2 ), about 60g / (h·m 2 )~about 70g / (h·m 2 ), about 60g / (h·m 2 )~about 80g / (h·m 2 ), about 60g / (h·m 2 )~about 90g / (h·m 2 ), about 60g / (h·m 2 )~about 100g / (h·m 2 ), about 70g / (h·m 2 )~about 80g / (h·m 2 ), about 70g / (h·m 2 )~about 90g / (h·m 2 ), about 70g / (h·m 2 )~about 100g / (h·m 2 ), about 80g / (h·m 2 )~about 90g / (h·m 2 ), about 80g / (h·m 2 )~about 100g / (h·m2 ), or approximately 90 g / (h m 2 ) ~ approx. 100g / (h m 2 ) of GO material per area of the first filter. In some embodiments of this aspect, the method can produce a throughput of about 25 g / (h m 2 ), approx. 30g / (h m 2 ), approx. 35g / (h m 2 ), approx. 40g / (h m 2 ), approx. 45g / (h m 2 ), approx. 50g / (h m 2 ), approx. 60g / (h m 2 ), approx. 70g / (h m 2 ), approx. 80g / (h m 2 ), approx. 90g / (h m 2 ), or approximately 100 g / (h m 2 ) first filter surface In some embodiments of this aspect, the method can produce a throughput of GO material per unit volume of at least about 25 g / (h m 2 ), at least about 30g / (h m 2 ), at least about 35g / (h m 2 ), at least about 40g / (h m 2 ), at least about 45g / (h m 2 ), at least about 50g / (h m 2 ), at least about 60g / (h m 2 ), at least about 70g / (h m 2 ), at least about 80g / (h m 2 ), at least about 90g / (h m 2 ), or at least about 100 g / (h m 2 ) of GO material per area of the first filter. In some embodiments of this aspect, the method can produce a throughput of up to about 25 g / (h m 2 ), up to about 30g / (h m 2 ), up to about 35g / (h m 2 ), up to about 40g / (h m 2 ), up to about 45g / (h m 2 ), up to about 50g / (h m2 ), up to about 60g / (h m 2 ), up to about 70g / (h m 2 ), up to about 80g / (h m 2 ), up to about 90g / (h m 2 ), or up to about 100 g / (h m 2 ) of GO material per area of the first filter can be produced.
[0062] A third aspect provided herein is a GO material comprising GO and water.
[0063] In some embodiments, the GO material is water-based. In some embodiments, the GO comprises single-layer GO. In some embodiments, the water-based material comprises an ink, a paste, a solution, a fluid, a liquid, a paint, a dye, a coating, or a compound.
[0064] In some embodiments, the GO material has a viscosity of about 800 m 2 / g ~ approx. 2,400m 2 In some embodiments, the GO material has a surface area of at least about 800 m / g. 2 / g. In some embodiments, the GO material has a surface area of up to about 2,400 m 2 / g. In some embodiments, the GO material has a surface area of about 800 m 2 / g ~ approx. 1,000m 2 / g, approx. 800m 2 / g ~ approx. 1,200m 2 / g, approx. 800m 2 / g ~ approx. 1,400m 2 / g, approx. 800m 2 / g ~ approx. 1,600m 2 / g, approx. 800m 2 / g ~ approx. 1,800m 2 / g, approx. 800m 2 / g ~ approx. 2,000m 2 / g, approx. 800m 2 / g ~ approx. 2,200m 2 / g, approx. 800m 2 / g ~ approx. 2,400m 2 / g, approx. 1,000m2 / g~about 1,200m 2 / g, about 1,000m 2 / g~about 1,400m 2 / g, about 1,000m 2 / g~about 1,600m 2 / g, about 1,000m 2 / g~about 1,800m 2 / g, about 1,000m 2 / g~about 2,000m 2 / g, about 1,000m 2 / g~about 2,200m 2 / g, about 1,000m 2 / g~about 2,400m 2 / g, about 1,200m 2 / g~about 1,400m 2 / g, about 1,200m 2 / g~about 1,600m 2 / g, about 1,200m 2 / g~about 1,800m 2 / g, about 1,200m 2 / g~about 2,000m 2 / g, about 1,200m 2 / g~about 2,200m 2 / g, about 1,200m 2 / g~about 2,400m 2 / g, about 1,400m 2 / g~about 1,600m 2 / g, about 1,400m 2 / g~about 1,800m 2 / g, about 1,400m 2 / g~about 2,000m 2 / g, about 1,400m 2 / g~about 2,200m 2 / g, about 1,400m 2 / g~about 2,400m 2 / g, about 1,600m 2 / g~about 1,800m 2 / g, about 1,600m 2 / g~about 2,000m 2 / g, about 1,600m 2 / g~about 2,200m 2 / g, about 1,600m 2 / g~about 2,400m 2 / g, approx. 1,800m 2 / g ~ approx. 2,000m 2 / g, approx. 1,800m 2 / g ~ approx. 2,200m 2 / g, approx. 1,800m 2 / g ~ approx. 2,400m 2 / g, approx. 2,000m 2 / g ~ approx. 2,200m 2 / g, approx. 2,000m 2 / g ~ approx. 2,400m 2 / g, or approximately 2,200 m 2 / g ~ approx. 2,400m 2 / g. In some embodiments, the GO material has a surface area of about 800 m 2 / g, approx. 1,000m 2 / g, approx. 1,200m 2 / g, approx. 1,400m 2 / g, approx. 1,600m 2 / g, approx. 1,800m 2 / g, approx. 2,000m 2 / g, approx. 2,200m 2 / g, or approximately 2,400 m 2 / g surface area.
[0065] In some embodiments, the GO material has a conductivity of about 0.1 S / m to about 5 S / m. In some embodiments, the GO material has a conductivity of at least about 0.1 S / m. In some embodiments, the GO material has a conductivity of up to about 5 S / m. In some embodiments, the GO material has a conductivity of about 0.1 S / m to about 0.2 S / m, about 0.1 S / m to about 0.5 S / m, about 0.1 S / m to about 0.75 S / m, about 0.1 S / m to about 1 S / m, about 0.1 S / m to about 2 S / m, about 0.1 S / m to about 3 S / m, about 0.1 S / m to about 4 S / m, about 0.1 S / m to about 5 S / m, about 0.2S / m to about 0.5S / m, about 0.2S / m to about 0.75S / m, about 0.2S / m to about 1S / m, about 0.2S / m to about 2S / m, about 0.2S / m~Approx. 3S / m, Approx. 0.2S / m~Approx. 4S / m, Approx. 0.2S / m~Approx. 5S / m, Approx. 0.5S / m~Approx. 0.75S / m, Approx. 0.5S / m~Approx. 1S / m, about 0.5S / m to about 2S / m, about 0.5S / m to about 3S / m, about 0.5S / m to about 4S / m, about 0.5S / m to about 5S / m, about 0.75 S / m ~ approx. 1S / m, approx. 0.75S / m ~ approx. 2S / m, approx. 0.75S / m ~ approx. 3S / m, approx. 0.75S / m ~ approx. 4S / m, approx. 0.75S / m ~ approx. 5S In some embodiments, the GO material has a conductivity of about 0.1 S / m, about 0.2 S / m, about 0.5 S / m, about 0.75 S / m, about 1 S / m, about 2 S / m, about 3 S / m, about 4 S / m, or about 5 S / m. In some embodiments, the GO material has a conductivity of at least about 0.1 S / m, at least about 0.2 S / m, at least about 0.5 S / m, at least about 0.75 S / m, at least about 1 S / m, at least about 2 S / m, at least about 3 S / m, at least about 4 S / m, or at least about 5 S / m. In some embodiments, the GO material has a conductivity of at most about 0.1 S / m, at most about 0.2 S / m, at most about 0.5 S / m, at most about 0.75 S / m, at most about 1 S / m, at most about 2 S / m, at most about 3 S / m, at most about 4 S / m, or at most about 5 S / m.
[0066] In some embodiments, the GO material has a C:O mass ratio of about 1:3 to about 5:1. In some embodiments, the GO material has a C:O mass ratio of at least about 1:3. In some embodiments, the GO material has a C:O mass ratio of up to about 5:1. In some embodiments, the GO material has a C:O mass ratio of about 1:3 to about 1:2, about 1:3 to about 1:1, about 1:3 to about 2:1, about 1:3 to about 3:1, about 1:3 to about 4:1, about 1:3 to about 5:1, about 1:2 to about 1:1, about 1:2 to about 2:1, about 1:2 to about 3:1, about 1:2 to about 4:1, about 1:2 to about 5:1, about 1:1 to about 2:1, about 1:1 to about 3:1, about 1:1 to about 4:1, about 1:1 to about 5:1, about 2:1 to about 3:1, about 2:1 to about 4:1, about 2:1 to about 5:1, about 3:1 to about 4:1, about 3:1 to about 5:1, or about 4:1 to about 5:1. In some embodiments, the GO material has a C:O mass ratio of about 1:3, about 1:2, about 1:1, about 2:1, about 3:1, about 4:1, or about 5:1. In some embodiments, the GO material has a C:O mass ratio of at least about 1:3, at least about 1:2, at least about 1:1, at least about 2:1, at least about 3:1, at least about 4:1, or at least about 5:1. In some embodiments, the GO material has a C:O mass ratio of up to about 1:3, up to about 1:2, up to about 1:1, up to about 2:1, up to about 3:1, up to about 4:1, or up to about 5:1.
[0067] In some embodiments, the GO material has an oxidation rate of about 15% to about 60%. In some embodiments, the GO material has an oxidation rate of at least about 15%. In some embodiments, the GO material has an oxidation rate of up to about 60%. In some embodiments, the GO material is about 15% to about 20%, about 15% to about 25%, about 15% to about 30%, about 15% to about 35%, about 15% to about 40%, about 15% to about 45%, about 15% to about 50%, about 15% to about 55%, about 15% to about 60%, about 20% to about 25%, about 20% to about 30%, about 20% to about 35%, about 20% to about 40%, about 20% to about 45%, about 20% to about 50%, about 20% to about 55%, about 20% to about 60%, about 25% to about 30%, about 25% to about 35%, about 25% to about 40%, about 25% to about 45%, about 25% to about 50%, about 25% to about 55%, about 25 ... The oxidation rate is about 60%, about 30% to about 35%, about 30% to about 40%, about 30% to about 45%, about 30% to about 50%, about 30% to about 55%, about 30% to about 60%, about 35% to about 40%, about 35% to about 45%, about 35% to about 50%, about 35% to about 55%, about 35% to about 60%, about 40% to about 45%, about 40% to about 50%, about 40% to about 55%, about 40% to about 60%, about 45% to about 50%, about 45% to about 55%, about 45% to about 60%, about 50% to about 55%, about 50% to about 60%, or about 55% to about 60%. In some embodiments, the GO material has an oxidation rate of about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, or about 60%. In some embodiments, the GO material has an oxidation rate of at least about 15%, at least about 20%, at least about 25%, at least about 30%, at least about 35%, at least about 40%, at least about 45%, at least about 50%, at least about 55%, or at least about 60%. In some embodiments, the GO material has an oxidation rate of up to about 15%, up to about 20%, up to about 25%, up to about 30%, up to about 35%, up to about 40%, up to about 45%, up to about 50%, up to about 55%, or up to about 60%.
[0068] In some embodiments, one of the electrical conductivity, surface area, C:O ratio, and oxidation rate of the GO material is measured by methylene blue absorption.
[0069] In some embodiments, the weight percent of GO in the GO material is about 10% to about 50%. In some embodiments, the weight percent of GO in the GO material is at least about 10%. In some embodiments, the weight percent of GO in the GO material is up to about 50%. In some embodiments, the weight percent of GO in the GO material is about 10% to about 15%, about 10% to about 20%, about 10% to about 25%, about 10% to about 30%, about 10% to about 35%, about 10% to about 40%, about 10% to about 45%, about 10% to about 50%, about 15% to about 20%, about 15% to about 25%, about 15% to about 30%, about 15% to about 35%, about 15% to about 40%, about 15% to about 45%, about 15% to about 50%, about 20% to about 25%, about 20% to about 30%, or about 30% to about 50%. %, about 20% to about 35%, about 20% to about 40%, about 20% to about 45%, about 20% to about 50%, about 25% to about 30%, about 25% to about 35%, about 25% to about 40%, about 25% to about 45%, about 25% to about 50%, about 30% to about 35%, about 30% to about 40%, about 30% to about 45%, about 30% to about 50%, about 35% to about 40%, about 35% to about 45%, about 35% to about 50%, about 40% to about 45%, about 40% to about 50%, or about 45% to about 50%. In some embodiments, the mass percentage of GO in the GO material is about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, or about 50%.
[0070] In some embodiments, the viscosity of the GO material is from about 10 centipoise to about 10,000 centipoise. In some embodiments, the viscosity of the GO material is at least about 10 centipoise. In some embodiments, the viscosity of the GO material is up to about 10,000 centipoise. In some embodiments, the viscosity of the GO material is from about 10 centipoise to about 20 centipoise, from about 10 centipoise to about 50 centipoise, from about 10 centipoise to about 100 centipoise, from about 10 centipoise to about 200 centipoise, from about 10 centipoise to about 500 centipoise, from about 10 centipoise to about 1,000 centipoise, from about 10 centipoise to about 2,000 centipoise, from about 10 centipoise to about 5,000 centipoise, from about 10 centipoise to about 10,000 centipoise, About 20 centipoise to about 50 centipoise, about 20 centipoise to about 100 centipoise, about 20 centipoise to about 200 centipoise, about 20 centipoise to about 500 centipoise, about 20 centipoise to about 1,000 centipoise, about 20 centipoise to about 2,000 centipoise, about 20 centipoise to about 5,000 centipoise, about 20 centipoise to about 10,000 centipoise, about 50 centipoise to about 100 centipoise, about 50 centipoise to about 200 centipoise, About 50 centipoise to about 500 centipoise, about 50 centipoise to about 1,000 centipoise, about 50 centipoise to about 2,000 centipoise, about 50 centipoise to about 5,000 centipoise, about 50 centipoise to about 10,000 centipoise, about 100 centipoise to about 200 centipoise, about 100 centipoise to about 500 centipoise, about 100 centipoise to about 1,000 centipoise, about 100 centipoise to about 2,000 centipoise, about 100 centipoise to about 5,000 centipoise, about 100 centipoise to about 10,000 centipoise, about 200 centipoise to about 500 centipoise, about 200 centipoise to about 1,000 centipoise, about 200 centipoise to about 2,000 centipoise, about 200 centipoise to about 5,000 centipoise, about 200 centipoise to about 10,000 centipoise, about 500 centipoise to about 1,000 centipoise, about 500 centipoise to about 2,000 centipoise, about 500 centipoise to about 5,000 centipoise, about 500 centipoise to about 10,000 centipoise, about 1,000 centipoise to about 2,000 centipoise, about 1,000 centipoise to about 5,000 centipoise, about 1,000 centipoise to about 10,000 centipoise, about 2,000 centipoise to about 5,000 centipoise, about 2,000 centipoise to about 10,000 centipoise, or about 5,000 centipoise to about 10,000 centipoise. In some embodiments, the viscosity of the GO material is about 10 centipoise, about 20 centipoise, about 50 centipoise, about 100 centipoise, about 200 centipoise, about 500 centipoise, about 1,000 centipoise, about 2,000 centipoise, about 5,000 centipoise, or about 10,000 centipoise. In some embodiments, the viscosity of the GO material is at least about 10 centipoise, at least about 20 centipoise, at least about 50 centipoise, at least about 100 centipoise, at least about 200 centipoise, at least about 500 centipoise, at least about 1,000 centipoise, at least about 2,000 centipoise, at least about 5,000 centipoise, or at least about 10,000 centipoise. In some embodiments, the viscosity of the GO material is at most about 10 centipoise, at most about 20 centipoise, at most about 50 centipoise, at most about 100 centipoise, at most about 200 centipoise, at most about 500 centipoise, at most about 1,000 centipoise, at most about 2,000 centipoise, at most about 5,000 centipoise, or at most about 10,000 centipoise.
[0071] In some embodiments, the GO material is a powder. In some embodiments, the GO material is anhydrous, intercalated, exfoliated, or any combination thereof. In some embodiments, the GO powder comprises single-layer GO. In some embodiments, the GO powder is dispersible in water, polar solvents, or any combination thereof.
[0072] In some embodiments, the weight percent of GO in the GO material is about 30% to about 95%. In some embodiments, the weight percent of GO in the GO material is at least about 30%. In some embodiments, the weight percent of GO in the GO material is up to about 95%. In some embodiments, the weight percent of GO in the GO material is about 30% to about 35%, about 30% to about 40%, about 30% to about 45%, about 30% to about 50%, about 30% to about 55%, about 30% to about 60%, about 30% to about 65%, about 30% to about 70%, about 30% to about 75%, about 30% to about 80%, about 30% to about 95%, about 35% to about 40%, about 35% to about 45%, about 35% to about 50%, about 35% ~ about 55%, about 35% to about 60%, about 35% to about 65%, about 35% to about 70%, about 35% to about 75%, about 35% to about 80%, about 35% to about 95%, about 40% to about 45%, about 40% to about 50%, about 40% to about 55%, about 40% to about 60%, about 40% to about 65%, about 40% to about 70%, about 40% to about 75%, about 40% to about 80%, about 40% to about 95%, about 45% to about 50%, about 45% to about 55 %, about 45% to about 60%, about 45% to about 65%, about 45% to about 70%, about 45% to about 75%, about 45% to about 80%, about 45% to about 95%, about 50% to about 55%, about 50% to about 60%, about 50% to about 65%, about 50% to about 70%, about 50% to about 75%, about 50% to about 80%, about 50% to about 95%, about 55% to about 60%, about 55% to about 65%, about 55% to about 70%, about 55% to about 75%, about 5% to about 80%, about 55% to about 95%, about 60% to about 65%, about 60% to about 70%, about 60% to about 75%, about 60% to about 80%, about 60% to about 95%, about 65% to about 70%, about 65% to about 75%, about 65% to about 80%, about 65% to about 95%, about 70% to about 75%, about 70% to about 80%, about 70% to about 95%, about 75% to about 80%, about 75% to about 95%, or about 80% to about 95%. In some embodiments, the mass percentage of GO in the GO material is about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, or about 95%.
[0073] Other objectives and advantages of the embodiments described herein will be further appreciated and understood when considered in conjunction with the following description and the accompanying drawings. The following description may include specific details describing certain embodiments described herein, but this should not be interpreted as a limitation on the scope of the embodiments described herein, but rather as an illustration of some embodiments. For each embodiment described herein, many variations known to those skilled in the art are possible, as suggested herein. Various changes and modifications may be made within the scope of the embodiments described herein without departing from the spirit thereof. [Brief description of the drawings]
[0074] The features of the present disclosure are set forth with particularity in the appended claims. A better understanding of the features and advantages of the present disclosure can be obtained by reference to the following detailed description that sets forth illustrative embodiments, in which the principles of the embodiments are utilized, and the accompanying drawings or figures (also referred to herein as "FIG." and "FIGS.").
[0075] [Figure 1] FIG. 1 is a schematic diagram illustrating an exemplary dead-end filtration method for forming graphene oxide (GO) material, according to some embodiments. [Diagram 2] 1 is an image showing an exemplary gelled GO on a filter. [Diagram 3] FIG. 1 is a schematic illustrating an exemplary cross-flow filtration method for forming GO material, according to some embodiments. [Figure 4A] FIG. 1 is a schematic diagram illustrating an exemplary apparatus and method for dispersing a GO suspension onto a first filter, according to some embodiments. [Figure 4B] FIG. 1 is a schematic diagram illustrating an exemplary apparatus and method for dewatering a GO suspension on a first filter according to some embodiments. [Figure 4C] FIG. 1 is a schematic diagram illustrating an exemplary apparatus and method for filtering a GO solution through a first filter, according to some embodiments. [Figure 4D] FIG. 1 is a schematic diagram illustrating an exemplary apparatus and method for drying a GO suspension on a first filter according to some embodiments. [Diagram 5] 1 is an exemplary optical microscope image of an exemplary GO material according to some embodiments. [Figure 6A] 1 is a first optical microscope image of an exemplary GO paste according to some embodiments. [Figure 6B] 13 is a second optical microscope image of an exemplary GO paste according to some embodiments. [Figure 6C] 13 is a third optical microscope image of an exemplary GO paste according to some embodiments. [Figure 6D] 13 is a fourth optical microscope image of an exemplary GO paste according to some embodiments. [Figure 7] 1 is an image of an exemplary dry GO material according to some embodiments. [Figure 8] 1 is an exemplary image of an exemplary dry GO powder, according to some embodiments. [Figure 9A] 1 is a first optical microscope image of an exemplary powdered GO material according to some embodiments. [Figure 9B] 1 is a second optical microscope image of an exemplary powdered GO material according to some embodiments. [Figure 10A] 1 is a first high magnification scanning electron microscope (SEM) image of an exemplary GO material according to some embodiments. [Figure 10B] 1 is a second high magnification SEM image of an exemplary GO material according to some embodiments. [Figure 10C] 13 is a third high magnification SEM image of an exemplary GO material according to some embodiments. [Figure 10D] 13 is a fourth high magnification SEM image of an exemplary GO material according to some embodiments. [Figure 10E] 1 is a first low magnification SEM image of an exemplary GO material according to some embodiments. [Figure 10F]1 is a second low magnification SEM image of an exemplary GO material according to some embodiments. [Figure 11] 1 is a particle distribution chart of an exemplary GO material, according to some embodiments. [Figure 12] 1 is an X-ray diffraction graph of an exemplary GO material according to some embodiments. [Figure 13] 1 is a graph showing X-ray photoelectron spectroscopy measurements of an exemplary GO material, according to some embodiments. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0076] Provided herein are graphene materials, fabrication processes, and devices with improved performance. In some embodiments, the present disclosure provides graphene oxide (GO) materials and methods of forming GO materials. Such methods of forming GO materials avoid the shortcomings of current methods of formation. Additionally, methods of solvent-assisted purification and drying of GO are provided.
[0077] Various aspects of the disclosure described herein may be applied to any of the specific applications described below, or to any other type of manufacturing, synthesis, or processing setting. Manufacturing, synthesis, or processing of other materials may similarly benefit from the features described herein. For example, the methods, devices, and systems herein may be advantageously applied to the manufacturing (or synthesis) of various forms of graphene or GO. The embodiments described herein may be applied as stand-alone methods, devices, or systems, or as part of an integrated manufacturing or material (e.g., chemical) processing system. It should be understood that different aspects of the disclosure may be recognized individually, collectively, or in combination with each other.
[0078] Reference is now made to the Figures. It will be understood that the figures and features therein are not necessarily drawn to scale. The schematics, images, formulas, charts, and graphs referred to herein represent fabricated example devices that serve as representations of the appearance, properties, and functionality of devices produced by the example methods described herein.
[0079] While preferred embodiments have been shown and described herein, it will be apparent to those skilled in the art that such embodiments are provided by way of example only. Numerous variations, modifications, and substitutions will occur to those skilled in the art. It is understood that various alternatives to the embodiments described herein may be used.
[0080] GO is a layered material formed through the oxidation of graphite, consisting of hydrophilic oxygenated graphene sheets with oxygen functional groups on the basal planes and edges. GO contains a carbon-like graphene single lamellar structure, has numerous oxygen-containing functional groups, and can be dispersed in a variety of solvents. The unique properties of GO therefore enable numerous carbon-based applications such as nanocomposites, polymer composites, energy storage, and biomedical applications, as well as use as a surfactant or catalyst.
[0081] GO can currently be formed by the Hummers process, which uses concentrated sulfuric acid, sodium nitrate, and potassium permanganate to oxidize graphite. The modified Hummers process is a simplification of the original Hummers process, but all such current processes use K + , H + , Mn 2+ , and SO4 2- The Hummers process produces GO materials that contain high rates of by-products and impurities, including, but not limited to, . In some embodiments, these impurities reduce at least one of the electrical and chemical performance of GO. Additionally, GO formed by the Hummers process exhibits strong acidity (pH<0) and high salt concentrations of about 40 grams per liter (g / L) to about 55 g / L.
[0082] However, removing these performance-detrimental by-products is currently expensive, time-consuming, and water-intensive due to the hydrophilicity of GO. Filtration is further inhibited by the formation of charge-stabilized GO colloids or gels. Such colloids become more dispersive in water at higher GO concentrations, forming highly viscous GO solutions even at low GO concentrations. Thus, the combination of GO's high hydrophilicity and viscosity requires significant amounts of energy to remove impurity by-products during GO production.
[0083] Alternative filtration methods, such as dialysis, have been used to increase the throughput and efficiency of GO production. Dialysis is a process that separates molecules in a solution by differences in diffusion rates through a semipermeable membrane. However, such methods are very time intensive because the primary driving force for mass transfer of solutes through the dialysis membrane decreases significantly as the solution is purified and as the solute concentration across the membrane decreases. Thus, such methods may not be suitable for industrial-scale GO production, as multiple dialysis cycles are required to remove sufficient amounts of by-products.
[0084] FIG. 1 shows a schematic diagram of an exemplary dead-end filtration method for forming a GO material according to some embodiments. Provided herein is a first method for forming a purified GO material 100, the method including forming 110 a GO suspension 112, dehydrating 120 the GO suspension 112, forming a GO solution 140, and filtering 130 the GO solution 140. In some embodiments, the GO solution 140 includes a dehydrated GO suspension 122 and a solvent solution 132. In some embodiments, the first method for forming the purified GO material 100 includes forming 110 a GO suspension 112, dispersing the GO suspension 112 on a first filter 121, dehydrating 120 the GO suspension 112 through the first filter 121 to form a dehydrated GO suspension 122, forming a GO solution 140 including the dehydrated GO suspension 122 and the solvent solution 132, and filtering 130 the GO solution 140 through the first filter 121. Alternatively, in some embodiments, a first method of forming purified GO material 100 includes forming 110 a GO suspension 112, dispersing 112 on a first filter 121, dehydrating 120 the GO suspension 112 through the first filter 121 to form a dehydrated GO suspension 122, and filtering 130 the GO solution 140 through a second filter.
[0085] In some embodiments, the GO suspension 112 is dispersed onto a first filter 121 prior to dewatering 120 the GO suspension 112. In some embodiments, the GO suspension 112 is dewatered 120 through the first filter 121. In some embodiments, the GO suspension 112 is dewatered 120 through the first filter 121 to form a dewatered GO suspension 122. In some embodiments, filtering the GO solution 140 is performed. 30 includes filtering 130 the dehydrated GO suspension 122 and the solvent solution 132. In some embodiments, filtering 130 the GO solution 140 includes filtering 130 the dehydrated GO suspension 122 through a first filter 121. In some embodiments, filtering 130 the dehydrated GO suspension 122 includes filtering 130 the dehydrated GO suspension 122 and the solvent solution 132 through a first filter 121. Alternatively, in some embodiments, filtering 130 the dehydrated GO suspension 122 includes filtering 130 the dehydrated GO suspension 122 through a second filter. In some embodiments, filtering 130 the dehydrated GO suspension 122 includes filtering 130 the dehydrated GO suspension 122 and the solvent solution 132 through a second filter.
[0086] In some embodiments, GO suspension 112 includes GO 111. In some embodiments, forming GO 111 includes the Hummers process. In some embodiments, the mass percentage of GO 111 in GO suspension 112 is about 0.05% to about 2%. In some embodiments, dehydrating 120 reduces the volume of GO suspension 112 (e.g., by up to about 90%), which reduces the volume of solvent solution 132 and the time required for any post-filtration washing process. In some embodiments, the volume of solvent solution 132 depends on the initial volume of GO suspension 112.
[0087] As shown in FIG. 1, filtering 130 the GO solution 140 includes dead-end filtration. In some embodiments, dead-end filtration involves forcing the feed solution to flow directly into the filter, and the removed components accumulate in the feed solution. Stationary phase filtration methods such as dead-end filtration, in which the GO product remains stationary on the filter, allow for higher throughput than dynamic filtration means because no dilution process is required to maintain the low moisture content of the GO material. In some embodiments, the stationary retentate in many stationary phase filtration methods results in clogging and fouling of the filter, but the use of a solvent solution 132 prevents clogging and fouling and increases throughput. In some embodiments, a filter press is the device for dead-end filtration. In some embodiments, GO is purified using a filter press by transferring the GO slurry to a chamber lined with a microfilter, adding HCl or water, and pushing the liquid from the GO suspension through a filter cloth or membrane filter.
[0088] Alternatively, in some embodiments, dewatering 120 the GO suspension 112 includes centrifugal filtration, dead-end filtration, cross-flow filtration, stationary phase filtration, dynamic phase filtration, surface filtration, depth filtration, vacuum filtration, recirculation filtration, or any combination thereof. In some embodiments, diafiltration is a dilution process that uses a washing process to dilute the GO solution and a filtration process to recover only the GO. In some embodiments, the mass transfer rate of solutes during diafiltration can be mechanically controlled by applying hydraulic pressure to the filtration membrane. In some embodiments, the process of diafiltration includes using HCl to wash away alkali metal salts, and excess HCl maintains a low pH, such as 0, to suppress gelation of GO. Some embodiments further include washing the GO solution with water and dead-end or cross-flow filtration.
[0089] As seen in FIG. 1, the first filter 121 comprises a Buchner funnel. Alternatively, in some embodiments, at least one of the first filter 121 and the second filter comprises a surface filter, a sieve, a filter paper, a belt filter, a drum filter, a cross-flow filter, a screen filter, a depth filter, a polymeric membrane, a ceramic membrane, a stainless steel filter, a stainless steel mesh, a carbon fiber mesh, a microfilter, an ultrafiltration filter, a membrane, or any combination thereof. In some embodiments, the first filter 121 comprises a stainless steel, dead-end Buchner funnel. In some embodiments, the second filter is the first filter 121.
[0090] In some embodiments, the solvent solution 132 includes an organic solvent. In some embodiments, the solvent solution 132 includes a polar organic solvent. By using a polar solvent instead of or in addition to water, gelation of GO is significantly reduced, thus minimizing clogging of the first filter 121. In some cases, reduced clogging allows for high throughput and high efficiency without the need for additional corrosive or toxic chemicals. In some embodiments, the solvent solution 132 includes a polar protic solvent. In some embodiments, the solvent solution 132 includes a solvent that highly dissolves salts. In some embodiments, the solvent solution 132 includes a water-miscible solvent. In some embodiments, the solvent solution 132 includes a low viscosity solvent. In some embodiments, the solvent solution 132 includes a neutral pH solvent. In some embodiments, the solvent solution 132 includes a non-toxic solvent. In some embodiments, the solvent solution 132 is 1,2-dichloroethane, 1,2-dimethoxyethane, 1,4-dioxane, 1-butanol, 1-propanol, 2-(2-propyl)-5-methyl-cyclohexan-1-ol, 2-butanol, 2-butanone, 2-propanol, 3,7-dimethylocta-2,6-dien-1-ol, acetic acid, acetone, acetonitrile, alcohol, benzene, butan-1-ol, butane-1,2,3,4-tetraol, carbon tetrachloride, chlorobenzene, chloroform, cyclohexane, cyclohexane-1,2,3,4,5,6-hexol, dichloromethane, diethyl ether, diethylene glycol, diglyme, di methyl ether, dimethyl sulfoxide, dimethylformamide, ethane-1,2-diol, ethanol, ethyl acetate, ethylene glycol, formic acid, glycerin, heptane, heptane-1,2,3,4,5,6,7-heptol, hexadecan-1-ol, hexamethylphosphoramide, hexamethylphosphite triamide, hexane, hexane-1,2,3,4,5,6-hexol, isopropanol, methanol, methyl t-butyl ether, methylene chloride, m-xylene, n-butanol, nitromethane, N-methyl-2-pyrrolidinone, N-methyl-2-pyrrolidone, n-propanol, or any combination thereof.In some embodiments, the solvent is o-xylene, pentan-1-ol, pentane, pentane-1,2,3,4,5-pentol, petroleum ether, prop-2-en-1-ol, prop-2-yn-1-ol, propan-2-ol, propane-1,2,3-triol, propane-1,2-diol, p-xylene, pyridine, t-butyl alcohol, tetrahydrofuran, methanol, toluene, triethylamine, water, or any combination thereof.
[0091] In some embodiments, as the suspension is purified, the gelation of GO is enhanced, and the gelled GO cake blocks the filter pores and channels of conventional filters, which increases the energy consumption, maintenance, and time required to produce purified GO. Figure 2 shows an image of an exemplary gelled GO on a filter.
[0092] Some embodiments further include drying the GO solution 140. In some embodiments, drying the GO suspension is performed by air blowing, dry evaporation, oven heating, freeze drying, or any combination thereof. Dry evaporation can be performed at ambient or elevated temperatures. In some embodiments, drying the GO solution is performed by drying methods known to those skilled in the art. In some embodiments, air blowing is performed with a dry gas flow. In some embodiments, drying the GO solution 140 includes an air blowing process using a dry gas flow at a pressure of about 10 psi to about 30 psi. The use of the solvent solution 132 during dehydration 120 increases the throughput of the drying process. In some embodiments, freeze drying best preserves the physicochemical properties of GO compared to heat-based drying. However, the freeze drying process and storage of freeze-dried GO can cause the GO sheets to restack to form non-dispersible GO aggregates, making such a drying method not ideal. Furthermore, the freeze drying process presents an uneconomical cost / mass for high throughput manufacturing.
[0093] 3 shows a schematic diagram of an exemplary cross-flow filtration method for forming a GO material according to some embodiments. Provided herein is a second method for forming a purified GO material 200 that includes forming 210 a GO suspension 112, dehydrating 220 the GO suspension 112 to form a dehydrated GO suspension 122, forming a GO solution 140 comprising the dehydrated GO suspension 122 and a solvent solution 132, and filtering 230 the GO solution 140.
[0094] In some embodiments, GO suspension 112 is dispersed onto a first filter 121 prior to dewatering 220 the GO suspension 112. In some embodiments, GO suspension 112 is dewatered 220 through the first filter 121. In some embodiments, GO suspension 112 is dewatered 220 through the first filter 121 to form a dewatered GO suspension 122.
[0095] In some embodiments, filtering 230 the dehydrated GO suspension 122 includes cross-flow filtering at least one of the dehydrated GO suspension 122 and the solvent solution 132. In some embodiments, the cross-flow filtering includes filtering a tangentially flowing feed solution to separate a retentate 233 from a permeate 234. In some embodiments, the feed solution includes at least one of the dehydrated GO suspension 122 and the solvent solution 132. In some embodiments, the retentate 233 includes at least one of the GO 111 and the solvent solution 132. In some embodiments, the permeate 234 includes impurities. In some embodiments, the permeate 234 is discarded.
[0096] In some embodiments, filtering 230 the GO solution 140 includes cross-flow recirculation filtering 231 the GO solution 140. In some embodiments, filtering 231 the GO solution 140 includes adding retentate 233 to the GO solution 140.
[0097] In some embodiments, cross-flow recirculation filtering 231 the GO solution 140 reduces the energy consumption, maintenance, and time required to produce purified GO by preventing GO gelation. Even at low concentrations of GO111, gelation from colloid formation creates a highly viscous feed solution that blocks the filter pores and flow paths of conventional filters. However, by reintroducing the retentate 233 back into the GO solution 140, cross-flow recirculation filtering 231 ensures a continuous low concentration of GO111 throughout the filtration process. In some embodiments, cross-flow recirculation filtering 231 the GO solution 140 further includes adding a volume of the solvent solution 132 to the GO solution 140 equal to the volume of the permeate 234. In some embodiments, cross-flow recirculation filtering 231 the GO solution 140 further includes adding the solvent solution 132 to the GO solution 140 at a flow rate equal to the output flow rate of the permeate 234. In some embodiments, the total amount of solvent solution 132 added depends on the initial amount of GO111. In some embodiments, adding a volume of solvent solution 132 equal to the volume of permeate 234 to the GO solution 140 further ensures a continuous low concentration of GO 111 throughout the filtration process.
[0098] In some embodiments, a second method of forming purified GO material 100 includes forming a GO suspension 112, dispersing the GO suspension 112 on a first filter 121, dewatering 120 the GO suspension 112 through the first filter 121 to form a dehydrated GO suspension 122, forming a GO solution 140 including the dehydrated GO suspension 122 and a solvent solution 132, and cross-flow recirculation filtering 231 the dehydrated GO suspension 122 and the solvent solution 132, where the cross-flow recirculation filtering 231 includes adding retentate 233 to the GO suspension 112 and the solvent solution 132.
[0099] As seen in Figure 3, the first filter 121 comprises a Buchner funnel. Alternatively, in some embodiments, at least one of the first filter 121 and the second filter comprises a surface filter, a sieve, a filter paper, a belt filter, a drum filter, a crossflow filter, a screen filter, a depth filter, a polymeric membrane, a ceramic membrane, a stainless steel filter, a stainless steel mesh, a carbon fiber mesh, a microfilter, an ultrafiltration filter, a membrane, or any combination thereof. In some embodiments, the first filter 121 comprises a stainless steel, dead-end Buchner funnel.
[0100] In some embodiments, dewatering 220 the GO suspension 112 includes centrifugal filtration, dead-end filtration, cross-flow filtration, stationary phase filtration, dynamic phase filtration, surface filtration, depth filtration, vacuum filtration, recirculation filtration, or any combination thereof.
[0101] As seen in FIG. 3, the second filter comprises cross-flow filtration. Alternatively, in some embodiments, the second filter comprises a Buchner funnel, a surface filter, a sieve, a filter paper, a belt filter, a drum filter, a screen filter, a depth filter, a polymeric membrane, a ceramic membrane, a stainless steel filter, a stainless steel mesh, a carbon fiber mesh, a microfilter, an ultrafiltration filter, a membrane, or any combination thereof. In some embodiments, the cross-flow recirculation filtration 231 comprises flowing the feed solution parallel to the filter surface. In some embodiments, the occurrence of clogging and fouling of the filter in the cross-flow recirculation filtration 231 is less than dead-end filtration due to back-diffusion of contaminants controlled by the cross-flow velocity.
[0102] In some embodiments, the solvent solution 132 includes water for a period of time. In some embodiments, the solvent solution 132 includes a solvent for a period of time. In some embodiments, the solvent solution 132 includes water and a solvent for a period of time. In some embodiments, the period of time is at least about 5 minutes, at least 10 minutes, at least 20 minutes, at least 30 minutes, at least 40 minutes, at least 50 minutes, or at least about 60 minutes, and / or about 5 minutes or less, 10 minutes or less, 20 minutes or less, 30 minutes or less, 40 minutes or less, 50 minutes or less, or about 60 minutes or less. In some embodiments, the period of time is at least about 1 hour, at least 2 hours, at least 3 hours, at least 4 hours, at least 5 hours, at least 6 hours, at least 7 hours, at least 8 hours, at least 9 hours, at least 10 hours, at least 11 hours, or at least about 12 hours, and / or about 1 hour or less, 2 hours or less, 3 hours or less, 4 hours or less, 5 hours or less, 6 hours or less, 7 hours or less, 8 hours or less, 9 hours or less, 10 hours or less, 11 hours or less, or about 12 hours or less. In some embodiments, the solvent solution 132 comprises an organic solvent. In some embodiments, the solvent solution 132 comprises a polar organic solvent. The use of a polar solvent instead of or in addition to water significantly reduces gelation of the GO, thus minimizing clogging of the second filter. In some cases, the reduced clogging allows for high throughput and high efficiency without the need for additional corrosive or toxic chemicals. In some embodiments, the solvent solution 132 comprises a polar protic solvent. In some embodiments, the solvent solution 132 comprises a solvent that is highly salt-soluble. In some embodiments, the solvent solution 132 comprises a water-miscible solvent. In some embodiments, the solvent solution 132 comprises a low viscosity solvent. In some embodiments, the solvent solution 132 comprises a neutral pH solvent. In some embodiments, the solvent solution 132 comprises a non-toxic solvent.In some embodiments, the solvent solution 132 is 1,2-dichloroethane, 1,2-dimethoxyethane, 1,4-dioxane, 1-butanol, 1-propanol, 2-(2-propyl)-5-methyl-cyclohexan-1-ol, 2-butanol, 2-butanone, 2-propanol, 3,7-dimethylocta-2,6-dien-1-ol, acetic acid, acetone, acetonitrile, alcohol, benzene, butan-1-ol, butane-1,2,3,4-tetraol, carbon tetrachloride, chlorobenzene, chloroform, cyclohexane, cyclohexane-1,2,3,4,5,6-hexol, dichloromethane, diethyl ether, diethylene glycol, diglyme, di methyl ether, dimethyl sulfoxide, dimethylformamide, ethane-1,2-diol, ethanol, ethyl acetate, ethylene glycol, formic acid, glycerin, heptane, heptane-1,2,3,4,5,6,7-heptol, hexadecan-1-ol, hexamethylphosphoramide, hexamethylphosphite triamide, hexane, hexane-1,2,3,4,5,6-hexol, isopropanol, methanol, methyl t-butyl ether, methylene chloride, m-xylene, n-butanol, nitromethane, N-methyl-2-pyrrolidinone, N-methyl-2-pyrrolidone, n-propanol, or any combination thereof. In some embodiments, o-xylene, pentan-1-ol, pentane, pentane-1,2,3,4,5-pentol, petroleum ether, prop-2-en-1-ol, prop-2-yn-1-ol, propan-2-ol, propane-1,2,3-triol, propane-1,2-diol, p-xylene, pyridine, t-butyl alcohol, tetrahydrofuran, methanol, toluene, triethylamine, water, or any combination thereof.
[0103] In some embodiments, the GO material is an aqueous GO material. In some embodiments, the aqueous material comprises an ink, a paste, a solution, a fluid, a liquid, a paint, a dye, a coating, or a compound. In some embodiments, the GO material can be drop cast onto a substrate. In some embodiments, the substrate is a silicon wafer. In some embodiments, the drop cast GO material is then coated with silicon dioxide.
[0104] Some embodiments further include drying the solvent solution 132, the GO suspension 122, and the retentate 233. In some embodiments, the drying is performed by air blowing, dry evaporation, oven heating, freeze drying, or any combination thereof. In some embodiments, the drying of the GO suspension is performed by a drying method known to one of skill in the art. In some embodiments, the dry evaporation is performed at ambient temperature. In some embodiments, the air blowing is performed with a dry gas flow. In some embodiments, the air blowing is performed with a dry gas flow at a pressure of about 10 psi to about 30 psi. In some embodiments, the use of a solvent solution during dehydration increases the throughput of the drying process. In some embodiments, freeze drying best preserves the physicochemical properties of GO compared to heat-based drying. However, the freeze drying process and storage of freeze-dried GO restacks the GO sheets to form non-dispersible GO aggregates, making such a drying method not ideal. Furthermore, the freeze drying process represents an uneconomical cost / mass for high throughput manufacturing.
[0105] In some embodiments, the methods described herein do not require any acid solution, such as HCl, to inhibit GO gelation. In some embodiments, the methods do not require a pure polar solvent as the washing solution, but instead can apply a solvent-water mixture. By using a solvent-water mixture as the washing solution, the method benefits from increased salt solubility of the washing solution while still inhibiting GO gelation.
[0106] FIG. 4A shows a schematic diagram of an exemplary apparatus and method for dispersing a GO suspension on a first filter, according to some embodiments. FIG. 4A shows the dispersion of GO suspension 301 on first filter 311 of apparatus 300. According to FIG. 4A, GO suspension 301 is dispersed on first filter 311 with a uniform thickness 301a. Alternatively, in some embodiments, GO suspension 301 is dispersed on first filter 311 with a non-uniform thickness. In some embodiments, GO suspension 301 is dispersed on first filter 311 with a uniform thickness 301a, where thickness 301a corresponds to the surface area on first filter 311. In some embodiments, the ratio between the uniform thickness 301a of GO suspension 301 and the surface area on first filter 311 is about 20:1 to about 1:20. In some embodiments, the ratio between the uniform thickness 301a of the GO suspension 301 and the surface area on the first filter 311 is about 20:1, about 10:1, about 5:1, about 4:1, about 3:1, about 2:1, about 1:1, about 1:2, about 1:3, about 1:4, about 1:5, about 1:10, or about 1:20. In some embodiments, the mass of GO suspension per area of the first filter 311 is about 3 kilograms per square meter (kg / m 2 ) ~ approx. 30kg / m 2According to FIG. 4A, the first filter 311 comprises a planar filter. Alternatively, in some embodiments, the first filter 311 comprises a circular filter, a curved filter, and any combination thereof. In some embodiments, the first filter 311 comprises a Buchner funnel, a surface filter, a sieve, a filter paper, a belt filter, a drum filter, a cross-flow filter, a screen filter, a depth filter, a polymeric membrane, a ceramic membrane, a stainless steel filter, a stainless steel mesh, a carbon fiber mesh, a microfilter, an ultrafiltration filter, a membrane, or any combination thereof. In some embodiments, the first filter 311 comprises a stainless steel, dead-end Buchner funnel. In some embodiments, the first filter has a pore size of about 0.5 micrometers (μm) to about 100 μm. In some embodiments, the first filter 311 is removable from the device or embedded into the device.
[0107] FIG. 4B shows a schematic diagram of an exemplary apparatus and method for dewatering a GO suspension on a first filter, according to some embodiments. In some embodiments, dewatering GO suspension 301 on a first filter 311 forms dehydrated GO suspension 321. As seen in FIG. 4B, the solvent solution drained from GO suspension 301 is accumulated in reservoir 320. Alternatively, in some embodiments, the solvent solution drained from GO suspension 301 is discarded or reused. In some embodiments, by dewatering, the volume of GO suspension 301 is reduced (e.g., by up to about 90%), which reduces the volume of solvent solution and time required for any post-filtration washing process.
[0108] FIG. 4C shows a schematic diagram of an exemplary apparatus and method for filtering a GO solution through a first filter, according to some embodiments. According to FIG. 4C, in some embodiments, filtering the GO solution 140 through the first filter 311 includes dispersing a dehydrated GO suspension 331 onto the first filter 311 and dispersing a solvent 302 onto the first filter 311. Optionally, in some embodiments, filtering the GO solution 140 through the first filter 311 includes dispersing a dehydrated GO suspension 331 onto the first filter 311 and subsequently dispersing a solvent 302 onto the first filter 311. Alternatively, in some embodiments, filtering the GO solution 140 through the first filter 311 includes dispersing a dehydrated GO suspension 331 onto the first filter 311. In some embodiments, the first filter 311 is a second filter, where the second filter is equivalent to the first filter 311. In some embodiments, filtering the GO solution 140 through the first filter 311 includes vacuum filtration, where the apparatus 300 includes a pressure reducing device 350 that reduces pressure on the reservoir 320. In some embodiments, reducing pressure on the reservoir 320 is performed before dispersing the solvent 302, during dispersing the solvent 302, after dispersing the solvent 302, or any combination thereof. In some embodiments, the apparatus 300 further includes a pressure reducing device 350. As seen in FIG. 4C, the excess solvent 302 and any other impurities are collected in the reservoir 320. Alternatively, in some embodiments, the excess solvent 302 and any other impurities are discarded, refiltered, recycled, or any combination thereof. As shown in FIG. 4C, dispersing the solvent 302 onto the dehydrated GO suspension 331 on the first filter 311 can be performed using a dispersing device 340, where the apparatus 300 includes a dispersing device 340.
[0109] 4D shows a schematic diagram of an exemplary apparatus and method for drying a GO suspension on a first filter, according to some embodiments. As seen in FIG. 4D, drying the dehydrated GO suspension 331 and solvent 302 on the first filter 311 is performed by a dryer 360. Alternatively, in some embodiments, the dehydrated GO suspension 331 and solvent 302 are dried on the first filter 311. As shown in FIG. 4D, drying the solvent 302 and dehydrated GO suspension 331 can be performed using a dryer 360, and the apparatus 300 includes the dryer 360.
[0110] 4D, drying the dehydrated GO suspension 331 and solvent 302 forms GO powder 303. In some embodiments, GO powder 303 is anhydrous, intercalated, exfoliated, or any combination thereof. In some embodiments, GO powder 303 comprises single-layer GO. In some embodiments, GO powder 303 is dispersible in water, polar solvents, or any combination thereof. Alternatively, in some embodiments, the process of drying the dehydrated GO suspension 331 and solvent 302 on the first filter 311 forms an aqueous GO material.
[0111] In some embodiments, at least one of the first method and the second method has a viscosity of about 25 g / (h m 2 ) ~ approx. 100g / (h m 2 ) of GO material throughput per area of the first filter.
[0112] Optical and scanning electron microscope (SEM) images of an exemplary GO material are shown in Figures 5-10F. Figure 5 shows an exemplary optical microscope image of an exemplary GO material, according to some embodiments. In some embodiments, the GO material is about 800 μm thick. 2 / g ~ approx. 2,400m 2 / g surface area. In some embodiments, the GO material has a conductivity of about 0.1 S / m to about 5 S / m. In some embodiments, the GO material has a C:O mass ratio of about 1:3 to about 5:1. In some embodiments, the GO material has an oxidation rate of about 15% to about 60%. In some embodiments, the mass percentage of GO in the GO material is about 10% to about 50%.
[0113] In some embodiments, at least one of the first and second methods of forming a purified GO material forms an aqueous GO material. In some embodiments, the aqueous material includes an ink, a paste, a solution, a fluid, a liquid, a paint, a dye, a coating, or a compound. FIGS. 6A-6D show optical microscope images of an exemplary aqueous GO material, according to some embodiments. FIG. 6A is a first optical microscope image showing an exemplary GO paste, according to some embodiments. FIG. 6B shows a second optical microscope image of an exemplary GO paste, according to some embodiments. FIG. 6C shows a third optical microscope image of an exemplary GO paste, according to some embodiments. FIG. 6D shows a fourth optical microscope image of an exemplary GO paste, according to some embodiments. In some embodiments, the viscosity of the GO material is about 10 centipoise to about 10,000 centipoise.
[0114] In some embodiments, at least one of the first and second methods of forming a purified GO material further includes drying the GO material. In some embodiments, at least one of the first and second methods of forming a purified GO material forms anhydrous GO material. FIG. 7 shows an image of an exemplary dried GO material, according to some embodiments. FIG. 8 shows an exemplary image of an exemplary dried GO powder, according to some embodiments. In some embodiments, the GO powder is formed by drying an aqueous GO material. In some embodiments, the GO powder is anhydrous, intercalated, exfoliated, or any combination thereof. In some embodiments, the GO powder comprises single-layered GO. In some embodiments, the GO powder is dispersible in water, polar solvents, or any combination thereof. FIG. 9A shows a first optical microscope image of an exemplary powdered GO material, according to some embodiments. FIG. 9B shows a second optical microscope image of an exemplary powdered GO material, according to some embodiments.
[0115] In some embodiments, the dried GO material is further processed by grinding, freezing, dispersing, or any combination thereof. Exemplary low and high magnification SEM images of GO materials are shown in Figures 10A-10F. Figure 10A shows a first high magnification SEM image of an exemplary GO material according to some embodiments. Figure 10B shows a second high magnification SEM image of an exemplary GO material according to some embodiments. Figure 10C shows a third high magnification SEM image of an exemplary GO material according to some embodiments. Figure 10D shows a fourth high magnification SEM image of an exemplary GO material according to some embodiments. Figure 10E shows a first low magnification SEM image of an exemplary GO material according to some embodiments. Figure 10F shows a second low magnification SEM image of an exemplary GO material according to some embodiments.
[0116] Electrochemical characterization according to Figures 11-13 shows the exceptional performance of the exemplary GO samples formed by the methods herein. Figure 11 is a chart showing the particle distribution of an exemplary GO material according to some embodiments. According to Figure 11, the GO material has particles ranging from about 2 μm to about 50 μm in size, exhibiting a modal particle size of about 4 μm. The particle size measurements are consistent with the particles seen in Figures 10A-10F. The particle size distribution of the GO material can be determined by measuring static light scattering of a dilute solution of the homogeneously dispersed GO material.
[0117] FIG. 12 shows an X-ray diffraction graph of an exemplary GO material, according to some embodiments. The X-ray diffraction graph of the GO material can be obtained by measuring the spectrum of purified GO material drop-cast onto zero background silicon with a 15 minute scan from 0-40 degrees 2θ. FIG. 12 shows an X-ray diffraction graph of an exemplary GO material, according to some embodiments. FIG. 13 shows an X-ray photoelectron spectroscopy measurement of an exemplary GO material, according to some embodiments. The X-ray photoelectron spectroscopy measurement was performed on a purified GO sample drop-cast onto copper tape. EXAMPLES
[0118] Example 1: Centrifugation / dead-end filtration The GO material is formed by preparing a GO suspension by a modified Hummers method. The GO suspension is dewatered using centrifugation or dead-end filtration. The dewatered GO suspension is transferred to a microfilter and washed with a solvent-water mixture under vacuum, whereby a purified GO cake is then removed from the microfilter.
[0119] Example 2: Cross-flow filtration The GO material is formed by preparation of a GO suspension by a modified Hummers method. The GO suspension is dehydrated using centrifugation or dead-end filtration. The dehydrated GO is diluted in a process reservoir with a sufficient volume of solvent-water mixture to achieve the initial volume of the GO suspension before dehydration. The GO and solvent-water mixture are filtered through a cross-flow microfilter by a Teflon diaphragm recirculation pump and returned to the process reservoir at a controlled flow rate and pressure to separate the retentate from the permeate. In some embodiments, the solvent-water mixture is continuously added to the process reservoir at a flow rate based on the permeate flow rate as the GO recirculation through the microfilter generates a permeate flow. In some cases, the total amount of solvent-water mixture added depends on the initial GO amount. In some cases, the permeate is discarded.
[0120] Example 3: Air blow drying The purified GO cake on the microfilter is rinsed with a pure polar solvent to dehydrate the GO cake. The dehydrated GO cake is then air-blowed at ambient temperature to facilitate evaporation of any residual solvent from the GO cake.
[0121] Example 4: GO Sheets In a fourth example, exemplary sheets, flakes of GO material are formed by drop-casting the GO material onto a silicon wafer, drying the GO material and wafer for a period of about 12 hours, and coating the dried GO material with a thin layer of silicon dioxide. In some embodiments, exemplary optical microscope images of the devices formed thereby display the lateral size distribution of the GO sheets.
[0122] While preferred embodiments of the present disclosure have been shown and described herein, it will be apparent to those skilled in the art that such embodiments are provided by way of example only. Numerous variations, changes, and substitutions will occur to those skilled in the art without departing from the present disclosure. It is understood that various alternatives to the embodiments of the disclosure described herein may be used in implementing the embodiments described herein. The following claims define the scope of the present disclosure, and it is intended that methods and structures within the scope of these claims, and their equivalents, be covered thereby.
[0123] Terms and Definitions Unless otherwise specified, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. As used in this specification and the appended claims, the singular forms "a", "an" and "the" include plural references unless the context clearly dictates otherwise. As used herein, any reference to "or" is intended to include "and / or" unless otherwise specified.
[0124] As used herein, and unless otherwise specified, the term "about" refers to a range of values within plus and / or minus 10% of a particular value.
[0125] As used herein, and unless otherwise specified, the term "GO" refers to graphene oxide.
[0126] As used herein, and unless otherwise specified, the term "solvent" refers to a substance that dissolves a solute, resulting in a solution.
[0127] As used herein, and unless otherwise specified, the term "polar solvent" refers to a solvent with a large dipole moment containing bonds between atoms of widely differing electronegativities.
[0128] As used herein, and unless otherwise specified, the term "polar protic solvent" refers to a solvent that solvates anions through hydrogen bonding.
[0129] As used herein, and unless otherwise specified, the term "alcohol" refers to an organic compound in which a hydroxyl functional group (-OH) is bonded to a saturated carbon atom.
[0130] As used herein, and unless otherwise specified, the term "centrifugal filtration" refers to the application of centrifugal force to the sedimentation of a heterogeneous mixture in a centrifuge to separate two miscible substances. Refers to a process that involves
[0131] As used herein, and unless otherwise specified, the term "filter" refers to a semi-permeable membrane.
[0132] As used herein, and unless otherwise specified, the term "dead-end filtration" refers to a process of filtration that involves passing a feed solution vertically through a filter, preventing retentate from flowing through the filter and allowing permeate to flow through the filter.
[0133] As used herein, and unless otherwise specified, the term "cross-flow filtration" refers to a process of filtration that involves passing a feed solution tangentially through a filter, preventing retentate from flowing through the filter and allowing permeate to flow through the filter.
[0134] As used herein, and unless otherwise specified, the term "surface filtration" refers to a process of filtration that involves passing a feed solution through a solid sieve, preventing the flow of retentate through the solid sieve and allowing the flow of permeate through the solid sieve.
[0135] As used herein, and unless otherwise specified, the term "depth filtration" refers to a process of filtration that involves passing a feed solution through a bed of particulate material, preventing retentate from flowing through the bed and allowing permeate to flow through the bed.
[0136] As used herein, and unless otherwise specified, the term "vacuum filtration" refers to a process of filtration that involves applying pressure to a feed solution to force it through a filter, preventing retentate from flowing through the filter and allowing permeate to flow through the filter.
[0137] As used herein, and unless otherwise specified, the term "recirculation filtration" refers to a process of filtration that involves passing a feed solution through a filter, preventing retentate from flowing through the filter, allowing permeate to flow through the filter, and in which the retentate or permeate is recirculated back into the feed solution.
[0138] As used herein, and unless otherwise specified, the term "Buchner funnel" refers to a funnel containing a filter or filter paper.
[0139] As used herein, and unless otherwise specified, the term "belt filter" refers to a filter that includes a pair of filter fabrics and a belt that passes through a system of rollers.
[0140] As used herein, and unless otherwise specified, the term "drum filter" refers to a drum, the walls of which include a semi-permeable membrane that rotates to filter the media therein.
[0141] As used herein, and unless otherwise specified, the term "microfilter" refers to a filter having a pore size of about 0.1 μm to about 10 μm.
[0142] As used herein, and unless otherwise specified, the term "ultrafiltration filter" refers to a filter having a pore size of about 0.01 μm to about 0.1 μm.
[0143] Although preferred embodiments of the methods and apparatus taught herein have been shown and described herein, it will be apparent to those skilled in the art that such embodiments are provided by way of example only. Numerous variations, changes, and substitutions will occur to those skilled in the art without departing from the methods and apparatus taught herein. It should be understood that various alternatives to the embodiments of the methods and apparatus taught and described herein may be used in implementing the methods and apparatus taught herein. The following claims define the scope of the methods and apparatus taught herein, and it is intended that methods and structures within the scope of these claims, and their equivalents, be covered thereby.
[0144] Other Non-Limiting Embodiments Graphene oxide is a layered material consisting of hydrophilic oxygen-containing graphene sheets. GO sheets generally have oxygen functional groups on the basal planes and edges. GO is usually obtained by strong oxidation of graphite, which subsequently transforms the hydrophobic graphite into hydrophilic GO. Since the breakthrough discovery of graphene, great attention has been paid to GO as a synthetic precursor for the large-scale chemical production of graphene. GO is characterized by a carbon-like graphene single lamellar structure. However, unlike graphene, GO has many oxygen-containing functional groups, which makes it dispersible in various types of solvents. The unique properties of GO allow it to be used for many promising carbon-based applications and as an excellent graphene precursor. GO has been used in nanocomposites, polymer composites, energy storage, and biomedical applications, in catalysis, and as a surfactant.
[0145] The most common method for producing GO is a modification of the Hummers process. The original method was developed by Hummers and Offeman and required concentrated sulfuric acid, sodium nitrate, and potassium permanganate to oxidize graphite. Since then, the reaction has been modified and simplified in many ways by many different researchers, but in every case, the by-products and impurities outnumber the GO product by several times by a number of ions (e.g., K + , H + , Mn 2+ , and SO4 2- ). This large amount of impurities, present as ionic species in the slurry, made purification of this highly useful product very time, energy, and water intensive. The oxygen functionality on the GO surface makes the product very hydrophilic, making normal filtration methods such as dead-end filtration excessively slow. Making the problem more difficult is that GO forms charge-stabilized colloids that become more dispersive in water as the purity of the solution increases. This leads to a very viscous solution, even at concentrations as low as 2 wt%, which cannot flow easily, leading to more advanced filtration techniques such as tangential flow filtration, which are very energy intensive.
[0146] Purification is an essential step to ensure the stability and safety of the final GO product. Several downstream applications of GO cannot tolerate even small concentrations of impurities. In fact, purification is often considered the main challenge for the industrial production of GO, mainly due to its unique chemical properties. To remove the large amount of impurities present in the reaction solution, GO is usually subjected to either dialysis or diafiltration.
[0147] Dialysis is commonly used to purify GO suspensions in laboratory applications due to its ease of operation. However, dialysis is usually considered an extremely slow process because the main driving force for mass transfer of solutes through the dialysis membrane decreases significantly as the solution is purified and also as the difference in free solute concentration on both sides of the membrane is reduced. Due to the slow mechanism of dialysis, the process requires days, and often weeks, to complete purification. Therefore, it is not suitable for industrial-scale GO production.
[0148] Diafiltration is a dilution process that uses a cleaning process along with a filtration process. Diafiltration typically uses a micro-permeable filter that separates suspended solids but not permeate salts. For diafiltration, the filtration process only recovers suspended solids (e.g., GO particles) while the washing process dilutes salts and suspended solids. As a result, GO diafiltration dilutes salts but maintains GO in the GO solution. Compared with dialysis, diafiltration requires much less time because the solute mass transfer rate in diafiltration can be mechanically controlled by the water pressure applied to the filtration membrane. There are various protocols for filtration and washing of GO. Usually, the alkali metal salts are first washed out using HCl, followed by thorough water washing. Excessive amounts of HCl are used to maintain a low pH around 0 to suppress GO gelation. Then, either dead-end filtration or cross-flow filtration is used to complete GO purification.
[0149] In dead-end filtration, all feed solution is forced to flow directly into the filter, and rejected components accumulate in the feed solution, thus accelerating filter clogging and fouling. In cross-flow filtration, the feed solution flows parallel to the filter surface, with the inlet feed stream entering the filtration module at a specific composition. Filter clogging and fouling are mitigated in cross-flow filtration due to enhanced back diffusion of contaminants, which is controlled by the cross-flow velocity.
[0150] A filter press is a conventional device for achieving dead-end filtration of slurry-type suspensions such as GO dispersions. For GO purification using a filter press, the GO slurry is first transferred into several chambers covered with microfilters. Then, HCl or water is added into the chambers, and the chambers are fully pressurized to push the liquid out of the GO suspension through the filter cloth or membrane filter.
[0151] Cross-flow filtration can also be applied to purify the GO suspension. In one embodiment, the GO slurry is first washed with HCl in a filter press. Cross-flow filtration can be used for subsequent washing with water. The HCl-washed GO slurry is transferred to a cross-flow filtration unit under a certain pressure level and washed with water, while the pressure filtration unit permeates the wastewater containing salt but not GO particles. Fresh wash water needs to be continuously added to the cross-flow filtration system at a flow rate comparable to the permeation rate of the wastewater. The GO suspension is purified through a cross-flow diafiltration unit until the impurities in the GO suspension are reduced to the desired level.
[0152] A challenge with GO filtration is that GO has a tendency to gel in aqueous media. As the suspension is refined and contains less salt, the gelation of GO intensifies. GO gelation significantly complicates filtration-based purification methods, as the gelled GO cake blocks the filter pores and flow channels of the filter module.
[0153] After the GO suspension is purified, it can be dried and converted to a solid form. Usually, vacuum freeze-drying is used to convert the GO suspension into a dry powder, despite its high cost on an industrial scale. Freeze-drying minimizes the changes in the physicochemical properties of GO compared to heat-based drying. However, it has been reported that commercially available freeze-dried GO loses its original dispersibility, thus limiting its use in some downstream applications. The freeze-drying process is believed to result in partial re-stacking of GO sheets, which forms GO aggregates that cannot be broken down during redispersion.
[0154] The above-mentioned shortcomings of conventional purification and drying methods are addressed in the present embodiments. It should be understood that both the following general description and the following detailed description are exemplary and explanatory only and are not limiting, as claimed. A solvent-assisted purification and drying method for GO is provided. The method utilizes a polar solvent to facilitate the GO filtration and GO drying processes. Compared with the use of pure water as a washing solution in GO filtration, the use of a polar solvent significantly reduces GO gelation, thus minimizing filter clogging due to gelled GO cake. The described method does not require any acid solution, such as HCl, to suppress GO gelation. The method does not necessarily require a pure polar solvent as a washing solution, and a solvent-water mixture can also be applied. With the use of a solvent-water mixture as a washing solution, the method benefits from increasing the salt solubility of the washing solution while still suppressing GO gelation. The polar solvent needs to have the following properties: high polarity, high salt solubility, good water miscibility, low viscosity, low toxicity, and neutral pH.
[0155] The present disclosure will be described in more detail by the following examples. It is to be understood that the above detailed description is illustrative and explanatory only and is not limiting as claimed.
[0156] The virgin GO suspension prepared by the modified Hummers method exhibits strong acidity (pH<0) and high salt concentration (40-55 g / L). The virgin GO suspension is dewatered using either centrifugation or dead-end filtration. The dewatering process results in a volume reduction of up to 90%, which minimizes the demand for the following washing process. The dewatered GO cake is placed on a microfilter and then washed with a solvent-water mixture under vacuum. The amount of washing with the solvent-water mixture depends on the initial GO amount. After the washing process, the purified GO cake is collected in the microfilter.
[0157] After the washing process as described above, the purified GO cake on the microfilter is further rinsed with pure polar solvent to dehydrate the GO cake. The dehydrated GO cake is air-blowed at ambient temperature to facilitate evaporation of any residual solvent from the GO cake. After air-blow, the ambient-dried GO cake is collected, which can be easily dispersed in pure water or polar solvent.
[0158] Virgin GO is prepared by a modified Hummers process. Virgin GO suspension is dewatered using either centrifugation or dead-end filtration. The dewatered GO cake is diluted with a solvent-water mixture to return to the initial volume of the virgin GO suspension. The diluted GO suspension is placed in a process reservoir connected to a cross-flow microfiltration unit through a recirculation pump. The pump circulates the diluted GO suspension at a controlled flow rate and pressure from the process reservoir through the microfilter back to the process reservoir. The GO recirculation through the microfilter generates a permeate flow while the solvent-water mixture is continuously added to the process reservoir with a flow rate based on the permeate flow. The total amount of solvent-water mixture added depends on the initial GO amount. After the diafiltration process, the purified GO suspension is recovered from the process reservoir.
[0159] Graphite oxide is a layered material consisting of hydrophilic oxygenated graphene sheets. The unique properties of GO allow it to be used for many promising carbon-based applications and as an excellent precursor to graphene. The purification step is essential to ensure the stability and safety of the final GO product. In fact, purification is often considered a major challenge for the industrial production of GO, mainly due to the extreme gelation of GO. Provided herein is a method that utilizes solvent-assisted purification and drying of GO. An exemplary method can utilize a polar solvent to facilitate the GO filtration process and the GO drying process. Compared to the use of pure water as a washing solution in GO filtration, the use of a polar solvent significantly reduces the gelation of GO, thus minimizing the clogging of the filter by the gelled GO cake. The method described herein does not necessarily use a pure polar solvent as the washing solution, and a solvent-water mixture can also be applied in the method. With the use of a solvent-water mixture as the washing solution, the method benefits from increasing the salt solubility of the washing solution while still suppressing the gelation of GO. The polar solvent should have the following properties: high polarity, high salt solubility, good water miscibility, low viscosity, low toxicity, and neutral pH. The following examples will explain the present disclosure in more detail. It should be understood that both the above detailed descriptions are exemplary and explanatory only, and are not limiting as claimed.
[0160] Example 1: Virgin GO suspensions prepared by the modified Hummers method exhibit strong acidity (pH<0) and high salt concentration (40-55 g / L). Virgin GO suspensions are dewatered using either centrifugation or dead-end filtration. The dewatering process results in a volume reduction of up to 90%, which minimizes the need for the following washing process. The dewatered GO cake is placed on a microfilter and then washed with a solvent-water mixture under vacuum. The amount of washing with the solvent-water mixture depends on the initial GO amount. After the washing process, the purified GO cake is collected in a microfilter.
[0161] Example 2: After the washing process in Example 1, the purified GO cake on the microfilter is further rinsed with pure polar solvent to dehydrate the GO cake. The dehydrated GO cake is air-blowed at ambient temperature to promote evaporation of any residual solvent from the GO cake. After air-blow, an ambient-dried GO cake is recovered, which is easily dispersible in pure water or polar solvent.
[0162] Example 3: Virgin GO is prepared by a modified Hummers process. Virgin GO suspension is dewatered using either centrifugation or dead-end filtration. The dewatered GO cake is diluted with a solvent-water mixture to return to the initial volume of the virgin GO suspension. The diluted GO suspension is placed in a process reservoir connected to a cross-flow microfiltration unit through a recirculation pump. The pump circulates the diluted GO suspension at a controlled flow rate and pressure from the process reservoir through the microfilter back to the process reservoir. The GO recirculation through the microfilter creates a permeate flow, while the solvent-water mixture is continuously added to the process reservoir with a flow rate based on the permeate flow. The total amount of solvent-water mixture added depends on the initial GO amount. After the diafiltration process, the purified GO suspension is collected in the process reservoir.
[0163] The most common method for producing GO is a modification of the Hummers process. The original method was developed by Hummers and Offeman and required concentrated sulfuric acid, sodium nitrate, and potassium permanganate to oxidize graphite. Since then, the reaction has been modified and simplified in many ways by many different researchers, but in every case, the by-products and impurities outnumber the GO product by several times with a number of ions (e.g., K + , H + , Mn 2+ , and SO4 2-). This large amount of impurities, present as ionic species in the slurry, made purification of this highly useful product very time, energy, and water intensive. The oxygen functionality on the GO surface makes the product very hydrophilic, making normal filtration methods such as dead-end filtration excessively slow. Making the problem more difficult is that GO forms charge-stabilized colloids that become more dispersive in water as the purity of the solution increases. This leads to a very viscous solution, even at concentrations as low as 2 wt%, which cannot flow easily, leading to more advanced filtration techniques such as tangential flow filtration, which are very energy intensive.
[0164] The purification step is essential to ensure the stability and safety of the final GO product. In fact, purification is often considered the main challenge for the industrial production of GO, mainly due to the unique chemical properties of GO. To remove the large amount of impurities present in the reaction solution, GO is usually subjected to either dialysis or diafiltration. However, dialysis is usually considered an extremely slow process because the main driving force for the mass transfer of solutes through the dialysis membrane decreases significantly as the solution is purified and also as the difference in free solute concentration on both sides of the membrane is reduced. Due to this slow mechanism of dialysis, the process requires a long time to complete the purification. It takes days, and often weeks, to complete. Therefore, it is not suitable for industrial-scale GO production. Diafiltration is a dilution process that uses a washing process along with a filtration process. For diafiltration, the washing process dilutes the salts and suspended solids, while the filtration process collects only the suspended solids (e.g., GO particles). As a result, GO diafiltration dilutes the salts but maintains the GO in the GO solution. Compared with dialysis, diafiltration requires much less time because the solute mass transfer rate in diafiltration can be mechanically controlled by the water pressure applied to the filtration membrane. The challenge of GO filtration is that GO tends to gel in aqueous media. As the suspension is refined and contains less salt, the gelation of GO is intensified. The gelation of GO significantly complicates filtration-based purification methods because the gelled GO cake blocks the filter pores and flow channels of the filter module. After the GO suspension is refined, it can be dried to convert it into a solid form. Vacuum freeze-drying is usually used to convert GO suspensions into dry powders, despite its high cost at industrial scale. This is because freeze-drying minimizes the changes in the physicochemical properties of GO compared to heat-based drying. However, it has been reported that commercially available freeze-dried GO loses its original dispersibility and thus has limited use in some downstream applications. The freeze-drying process is believed to result in partial re-stacking of GO sheets, which forms GO aggregates that cannot be broken down during redispersion. The above-mentioned shortcomings of conventional purification and drying methods are addressed in the present embodiments. The disclosed embodiments use solvent-assisted purification and drying of GO. The methods described herein utilize polar solvents to facilitate the GO filtration and GO drying processes. Compared to the use of pure water as a washing solution in GO filtration, the use of polar solvents significantly reduces the gelation of GO, thus minimizing the clogging of the filter by gelled GO cake. The embodiments provided herein enable the purification process to avoid the use of any acid solution, such as HCl, to suppress the gelation of GO.Diafiltration is the most common method to purify GO suspensions, and various protocols exist for filtration and washing of GO. Usually, alkali metal salts are first washed out using HCl, followed by thorough water washing. Excessive amount of HCl is used to maintain a low pH around 0 to suppress GO gelation. Then, either dead-end filtration or cross-flow filtration is used to complete GO purification. In dead-end filtration, all the feed solution is forced to flow directly into the filter, and the rejected components accumulate in the feed solution, thus accelerating filter clogging and fouling. In cross-flow filtration, the feed solution flows parallel to the filter surface, with the inlet feed stream entering the filtration module at a specific composition. Filter clogging and fouling are mitigated in cross-flow filtration due to enhanced back diffusion of contaminants, which is controlled by the cross-flow velocity. Filter presses are the conventional devices to achieve dead-end filtration of slurry-type suspensions such as GO dispersions. For GO purification using filter presses, the GO slurry is first transferred to several chambers covered with microfilters. HCl or water is then added into the chamber and the chamber is fully pressurized to push the liquid out of the GO suspension through the filter cloth or membrane filter. The challenge with GO filtration is that GO has a tendency to gel in aqueous media. As the suspension is refined and contains less salt, the gelation of GO intensifies. GO gelation significantly complicates filtration-based purification methods as the gelled GO cake blocks the filter pores and channels of the filter module.
Claims
1. 1. A method of forming a purified graphene oxide (GO) material, comprising: forming a first GO suspension comprising GO; dehydrating the first GO suspension using a first filter to form a dehydrated GO suspension; forming a second GO suspension comprising the dehydrated GO suspension and a solvent solution comprising a polar organic solvent; filtering the second GO suspension through a second filter to form the purified GO material, the filtration comprising centrifugal filtration, dead-end filtration, cross-flow filtration, stationary phase filtration, dynamic phase filtration, surface filtration, depth filtration, vacuum filtration, recirculation filtration, or any combination thereof; Drying the second GO suspension on the second filter. The above method.
2. 2. The method of claim 1, wherein filtering the second GO suspension comprises filtering the GO suspension through the second filter under water pressure.
3. 3. The method of claim 2, wherein filtering the second GO suspension comprises dead-end filtration and vacuum filtration, and the water pressure on the GO suspension is between 1 psi (6.9 kPa) and 5 psi (34.5 kPa).
4. 3. The method of claim 2, wherein filtering the second GO suspension comprises cross-flow recirculation filtration of the second GO suspension to form a retentate and a permeate, wherein the retentate is added to the second GO suspension.
5. 5. The method of claim 4, further comprising continuously adding a volume of the solvent solution to the second GO suspension during the cross-flow recirculation filtration of the second GO suspension.
6. 6. The method of claim 5, wherein the volume of the solvent solution is added to the second GO suspension at a solvent solution flow rate that is approximately the same as the permeate flow rate.
7. 6. The method of claim 5, wherein during a first period of time, the solvent solution comprises at least one of water and the polar organic solvent, and during a second period of time, the solvent solution comprises water or the polar organic solvent.
8. 2. The method of claim 1, wherein the weight percentage of the GO in the first GO suspension is between 0.05% and 2%.
9. 2. The method of claim 1, wherein dewatering the first GO suspension comprises centrifugal filtration, dead-end filtration, cross-flow filtration, stationary phase filtration, dynamic phase filtration, surface filtration, depth filtration, vacuum filtration, recirculation filtration, or any combination thereof.
10. The method of claim 1 , wherein the polar organic solvent solution comprises a protic solvent.
11. 2. The method of claim 1, wherein the weight percentage of the dehydrated GO suspension in the second GO suspension is between 10% and 60%.
12. The mass of the first GO suspension per area of the second filter is 3 kilograms per square meter (kg / m 2 ) ~ 30kg / m 2 The method of claim 1, wherein
13. 2. The method of claim 1 , wherein filtering the dehydrated GO suspension and the solvent solution comprises depositing the dehydrated GO suspension onto the second filter and then depositing the solvent solution onto the dehydrated GO suspension on the second filter.
14. 10. The method of claim 1, wherein at least one of the first filter and the second filter comprises a Buchner funnel, a surface filter, a sieve, a filter paper, a belt filter, a drum filter, a crossflow filter, a screen filter, a depth filter, a polymeric membrane, a ceramic membrane, a stainless steel filter, a stainless steel mesh, a carbon fiber mesh, a microfilter, an ultrafiltration filter, a membrane, or any combination thereof.
15. The method of claim 1 , wherein the second filter is the first filter.
16. 2. The method of claim 1, wherein drying the second GO suspension is performed by air blowing, dry evaporation, heating, oven heating, freeze drying, or any combination thereof.
17. 17. The method of claim 16, wherein the air blowing is performed with a dry gas stream at a pressure between 10 psi (68.9 kPa) and 30 psi (206.8 kPa).
18. The method of claim 16, wherein the heating is carried out at a temperature of from 10°C to 50°C.
19. 2. The method of claim 1, wherein the GO material comprises GO powder, anhydrous GO powder, intercalated GO powder, exfoliated GO powder, single layer GO material, water-dispersible GO material, polar solvent-dispersible GO material, water-based GO material, GO ink, GO paste, GO solution, GO fluid, GO liquid, GO paint, GO dye, GO coating, GO compound, or any combination thereof.
20. The purified GO material is 800 m 2 / g~2,400m 2 The method of claim 1 having a surface area of 1 / g.
21. 10. The method of claim 1, wherein the purified GO material has a conductivity of 0.1 Siemens per meter (S / m) to 5 S / m.
22. 2. The method of claim 1, wherein the purified GO material has an oxidation rate of 15% to 60%.
23. 2. The method of claim 1, wherein the polar organic solvent comprises ethyl acetate, tetrahydrofuran, dichloromethane, acetone, acetonitrile, dimethylformamide, dimethylsulfoxide, acetic acid, n-butanol, isopropanol, n-propanol, ethanol, methanol, formic acid, or any combination thereof.
24. The method of claim 1 , wherein the polar organic solvent comprises an alcohol.
25. The alcohol may be methanol, ethanol, propan-2-ol, butan-1-ol, pentan-1-ol, hexadecan-1-ol, ethane-1,2-diol, propane-1,2-diol, propane-1,2,3-triol, butane-1,2,3,4-tetraol, pentane-1,2,3,4,5-pentol, hexane-1,2,3,4,5,6-hexol, heptane-1,2,3,4,5,6,7-heptol, prop-2-en-1-ol, 3,7-dimethylocta-2,6-dien-1-ol, 25. The method of claim 24, comprising prop-2-yn-1-ol, cyclohexane-1,2,3,4,5,6-hexol, 2-(2-propyl)-5-methyl-cyclohexan-1-ol, or any combination thereof.
26. 10. The method of claim 1, wherein the first filter, the second filter, or both, have a pore size of 0.5 micrometers (μm) to 100 μm.
Citation Information
Patent Citations
Active carbon modifying device
CN106006632A
JP1973081170A
Production method of graphite oxide, and graphite oxide
JP2015160766A
How to generate graphene quantum dots from coal and coke
JP2016525997A
Method for producing graphene and graphene oxide from anthracite
JP2017503748A